Rational design of glucose-assisted hydrothermal Co-Ni-Al catalysts for the selective hydrodeoxygenation of vanillin to 4-methylcyclohexanol - Yuhao Shi; Weiping Tang; Fei Ge; Xiaohui Yang; Minghao Zhou (Biomass and Bioenergy, 2027)

Polygonatum cyrtonema polysaccharide-based emulsion coating for postharvest preservation of satsuma mandarin and the underlying dual omics mechanisms - Yan Shi; Chenyu Wang; Lei Huo; Yihan Wang; Pan Wang; Miaomiao Yao; Jinping Si; Huqing Yang; Wanying Ge (Postharvest Biology and Technology, 2027)

Impacts of pile-driving noise on neurotransmitter- and immune-parameters of the thick-shell mussel (Mytilus coruscus) - Maozhu Wang; Yingying Yu; Xinrui Ge; Chenhui Wu; Chenxin Gong; Kaiwen Hu; Haonan Bian; Yue Gu; Xinguo Zhao; Bin Li; Haibin Yu; Wei Shi; et al. (Marine Pollution Bulletin, 2026)

Soil salinity inversion and spatiotemporal dynamics in cotton fields in the Wei–Ku oasis - Jinming Zhang; Jianli Ding; Jinjie Wang; Zihan Zhang; Liya Shi; Xiangyu Ge (CATENA, 2026)

Side-stream blue light process washes out nitrite oxidizing bacteria via asymmetric photoprotection for partial nitrification in low ammonium wastewater - Weican Shi; Yue Zhuo; Kerui Tang; Yijie Yu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2026)

A SASP-related four-gene signature associated with intervertebral disc degeneration: integrated bioinformatics analysis and validation of pinocembrin as a therapeutic candidate - Ge-Liang Yao; Shi-Jiang Wang; Ying Zhang; Jia-Ming Liu; Hong-Hai Song; Zhi-Li Liu (Molecular Biology Reports, 2026)

Impacts of speed limits on emissions, energy consumption and traffic efficiency - Shi-Teng Zheng; Junfang Tian; Rui Jiang; Bin Jia; Ying-En Ge (Transportation Research Part D: Transport and Environment, 2026)

A well-log response-constrained EAHHO-PI-KAN method for shale mineral composition prediction - Qihui Li; Ning Wang; Xinmin Ge; Yiguo Chen; Cheng Zhai; Rengang Shi; Xiaorui Sui; Obay Salih (Journal of Applied Geophysics, 2026)

Spiro-donor modified blue thermally activated delayed fluorescence emitters with high efficiency, narrowband emission, and excellent lysosomal targeting ability - Deli Li; Qingchao Liu; Ruizhe Xu; Wei Liu; Rong Hu; Wei Li; Shi-Jian Su; Ziyi Ge; Yuhua Tong (Chemical Engineering Journal, 2026)

Targeted inhibition of JAK2 phosphorylation by GenX disrupts the JAK2-STAT3 pathway and induces cardiovascular toxicity in zebrafish: Insights from network toxicology and molecular dynamics - Yuzhi Zhao; Xiaoqiang Ge; Gaoyuan Wang; Qiaoling Zhang; Chengyu Geng; Zhongxiu Deng; Siyu Chen; Siyue Tan; Yifan Shi; Meng Zhao; Xinyi Wu; Shou-Lin Wang; et al. (Toxicology and Applied Pharmacology, 2026)

Experimental design and adsorption mechanism research of risedronate nanofunctionalized hydroxyapatite for efficient removal of Co2+ and Pb2+ - Jianzhe Ma; Juying Li; Mingxing Shi; Yuting Chu; Yueqing Zhang; Feng Ge; Mingzhu Xia; Fengyun Wang; Deyang Kong (Journal of Environmental Chemical Engineering, 2026)

Lattice carbon-induced electronic regulation of AlCo2O4 spinels for boosting toluene oxidation - Dadao Wang; Xueqin Yang; Mimi Wu; Menglan Xiao; Yanhu Zhang; Mianmian Zhang; Xiuhong Zhu; Guangxin Ru; Yucong Guo; Bo Shi; Xiaolin Yu; Maofa Ge (Journal of Environmental Chemical Engineering, 2026)

Ultrasound-assisted three-phase partitioning produces a pectin-leaning polysaccharide fraction from Idesia polycarpa Maxim cake meal with stable rheology and prebiotic-like potential - Yuanfu Zhang; Wenlin Zhang; Xin Shi; Longfeng Tan; Zhiyou Zhao; Yan Hu; Renshuai Huang; Yonghui Ge; Kewei Chen; Guangjing Chen (Food Chemistry, 2026)

Developmental neurotoxic effects of organophosphate flame retardants (OPFRs) across different life stages and the central role of pioneer transcription factors Neurog2/Ascl1 during the embryonic period - Kaidong Wang; Ge Shi; Yonghang Li; Yuxuan Jiao; Qianrong Zhang; Qi Liu; Chenyang Wu; Ai Qi; Min Huang (Environmental Pollution, 2026)

Synergistic mechanisms of coupled hydraulic fracturing and surfactant-enhanced extraction for the remediation of low-permeability organic-contaminated sites: a comprehensive numerical study - Shi-Jin Feng; Jiu-Ge Niu; Qi-Teng Zheng; Yun-Hui Zhang; Ya-Dong Zhou (Computers and Geotechnics, 2026)

Substantial mitigation of nitrous oxide realized in a light-mediated and aeration-free microalgal-bacterial consortium system - Lingfeng Wang; Weican Shi; Yanlin Liu; Zhaoming He; Jianhua Guo; Shijian Ge; Shuang Qiu (Algal Research, 2026)

Precisely engineering transglycosidases as robust biocatalysts toward glycoside reformation for innovative food processing - Jiawei Tang; Ao Li; Mengxiao Tang; Feiyin Ge; Lingyun Hu; Xiaodan Song; Xingyuan Liu; Hao Shi; Zhongbiao Tan (Critical Reviews in Food Science and Nutrition, 2026)

Pore fluid pH–salinity homogenization for sustained electroosmosis: Performance, energy efficiency and underlying mechanisms - Xiaojuan Yang; Ge Shi; Yuanqiang Cai; Ángel Yustres; Rubén López-Vizcaíno; Honglei Sun (Journal of Environmental Management, 2026)

Sustained activation of M1 microglia by oligomerized alpha-synuclein released from dopaminergic neuronal damage through CD11b/Src/Erk/NOX2 axis after Paraquat exposure - Qian Cai; Qianqian Jing; Ge Shi; Yaqin Liu; Liang Gong; Nan Chen; Min Huang (Toxicology, 2026)

Optimization design and process intensification of hydrolysis distillation process for toluene diisocyanate tar residue - Dandan Li; Yuxuan Zhang; Shi Zhao; Jijun Ge; Guoxuan Li; Rongshan Bi; Pan Xu (Process Safety and Environmental Protection, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

A review of machine learning applications in inland and nearshore water color remote sensing: from preprocessing to object detection and parameter estimation - Jiarui Shi; Zuchuan Li; Ge Liu; Chong Fang; Zhidan Wen; Yingxin Shang; Hui Tao; Sijia Li; Qiang Wang; Zijin Wang; Kaishan Song (Journal of Hydrology, 2026)

An end-to-end framework for semi-automated and cost-effective urban drainage system design: integrating deep learning, topology generation, and multi-objective optimization - Qianqian Zhou; Shuya He; Zihao Guan; Qisheng Zhong; Xiaoguang Ge; Jianliang Zhang; Qi Wang; Zhiwei Zhao; Huiting Shi (Journal of Hydrology, 2026)

6PPD and 6PPD-Q driven phytotoxicity in Eichhornia crassipes: From molecular damages to ecological potential implications - Yichen Ge; Weitao Liu; Xiang Li; Jinzheng Liu; Ruiying Shi; Xinwei Shi; Aurang Zeb; Qi Wang; Jianling Wang; Cuihong Chen; Yuebing Sun (Journal of Environmental Sciences, 2026)

A multispecies bioindication framework for assessing microplastic pollution in marine fish - FangKe Qi; Xingcheng Ge; Guangyao Xia; Chang Shi (Journal for Nature Conservation, 2026)

Experimental study on the influence of confining pressure on borehole bottom rock damage in pneumatic down-the-hole hammer drilling - Pengyu Zhang; Jianming Peng; Yanliang Li; Yu Liu; Dong Ge; Baoyi Chen; Jiming Li; Boyu Shi; Zicheng Wang (Geothermics, 2026)

An engineering strategy from biomass support to a precision-recognition interface: amino acid-assisted imprinted polymers for protein adsorption - Xinya Xu; Yanhui Ge; Yundong Xie; Chuan Wang; Yongheng Shi; Jing Zhou; Jiping Liu (Food Chemistry, 2026)

Filler-free, small-molecule-induced hydrogen-bond reconstruction enables enhanced piezoelectric performance in polyamide 11 - Shu-Dan Ge; Xin Li; Min Jiang; Shi-Huan Tan; Xian-Yue Xiang; Si-Si Wang; Hai-Bo Zhao; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Solar-driven green degradation of lignin toward sustainable aromatics via BiVO4/Zn4In2S7 S-scheme heterojunction - Qunshuai Li; Luxin Zhang; Weiwei Shi; Sishang Ge; Menglu Hu; Rong Chen (Chemical Engineering Journal, 2026)

Modifying wood with a carboxymethyl-activated delignification/borate composite modifier to achieve high efficiency and salt-fouling resistance in solar evaporators - Kai Li; Hailing Shi; Ruihao Ge; Bin Wang; Kui Liu; Yixuan Wang; Fengyu Quan; Xing Tian; Yanzhi Xia (Bioresource Technology, 2026)

Fine-scale mapping of built-environment carbon emissions: A multi-source data fusion and explainable machine learning framework for high-density urban regions - Ge Shi; Haoran Tang; Wei Wang; Chuang Chen; Jiantao Shi; Bo Wang; Lin Sun (Building and Environment, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Selective regulation of partial nitrification/denitrification via light irradiation: Microbial niche differentiation and metabolic adaptation mechanisms - Yue Zhuo; Weican Shi; Kerui Tang; Yijie Yu; Shijian Ge; Shuang Qiu (Water Research, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Cotton solanesyl diphosphate synthases GhSPS1/2 catalyzes plastoquinone-9 (PQ-9) biosynthesis associating with photoprotection - Saisai Wang; Xiaoyang Ge; Gege Shi; Jingjing Zhan; Peng Wang; Ye Tang; Wanlong Bai; Jiahe Wu; Ge Zhao (Plant Science, 2026)

W-Doped Bi2O3 Photocatalyst Based on Bi-MOF: Enhanced Visible-Light-Driven Methylene Blue Degradation and Hydrogen Production via Electronic Structure Modulation - Keren Shi; Xiaoyu Li; Qiaowei Xiao; Ziyan Wang; Wende Yi; Shaoying Ge; Zhenrui Shi; Jianlin Ren; Fuke Wang; Zhiqiang Tian; Huiqin Yao (Journal of Environmental Chemical Engineering, 2026)

Molecular Evidence for Distinct Coastal Dissolved Organic Matter Responses to Nitrogen and Phosphorus Enrichment - Xin Guo; Junfeng Chen; Xiao Chen; Lianbao Zhang; Gang Li; Hongwei Ren; Bokun Chen; Yubin Hu; Ge Xu; Dingxi Zhang; Chen He; Quan Shi; et al. (Journal of Environmental Sciences, 2026)

Temperature-dependent KMnO4 oxidative decrosslinking for enhanced permeance and scaling resistance of polyamide nanofiltration membranes - Ning Ma; Ruirui Jiang; Jielin Shi; Xinwei Kang; Jinyu Li; Feiyue Ge; Feilong Zhang; Feiyong Chen; Daliang Xu; Xuewu Zhu (Desalination, 2026)

Precursor-regulated formation pathway of rutile VO2 for aqueous zinc-ion storage - Fanghua Liang; Chunqing Niu; Ling Wang; Junpeng Xiong; Azeem Ullah; Chunhong Zhu; Jian Shi; Mayakrishnan Gopiraman; Mingzheng Ge; Ick Soo Kim (Chemical Engineering Journal, 2026)

CHBP-loaded mesoporous polydopamine nanoparticles attenuate neuroinflammation and reprogram microglia-neuron crosstalk for spinal cord injury repair - Linyi Xiang; Jiacheng Zhang; Yuzhe Wu; Jingwei Shi; Yun Shu; Ruize Miu; Jiayi Zhao; Junsheng Zhu; Zhichao Tao; Yibo Geng; Haojie Zhang; Zhenglin Li; et al. (Chemical Engineering Journal, 2026)

Enhancing simultaneous nitrogen and phosphorus removal in secondary effluent by a novel coal gangue-sulfur autotrophic biofilter: performance and microbial mechanisms - Sijie Ge; Kexin Shang; Xin Wang; Limei Yuan; Tongtong Shi; Chuanyi Zhang (ENGINEERING Environment, 2026)

Energy Absorption Model and Mechanism of Abrasive Water Jet Cutting on Sandstone Under Stress Based on Cutting Striations - Yiyu Lu; Houhan Pu; Qinglin Deng; Zhaolong Ge; Zhuolin Shi; Jianming Shangguan; Yuhuai Cui; Zhi Yao; Yunliang Wang (Rock Mechanics and Rock Engineering, 2026)

Precise surface water mapping from SAR images in Kenya by a multi-scale attention network with hybrid dilated convolution - Yong Li; Lulu Shi; Zhenrong Gu; Heiko Balzter; Vagner Ferreira; Ying Ge; Hongyan Wang; Huiyu Zhou; David Siriba; Haowei Wu; Xiangwen Shen; Xinzhe Zhao (International Journal of Remote Sensing, 2026)

Real-time sick fish detection system for aquaculture based on edge computing - Duanrui Wang; Fan Ge; Rui Xu; Xingyue Zhu; Hongjian Lv; Dianting Zeng; Meng Wu; Jiyang Yu; Weijian Cui; Qiwei Qin; Shaowen Wang; Yi Shi; et al. (Aquaculture, 2026)

Benzo[a]pyrene induces non-alcoholic fatty liver disease by exacerbating hepatic senescence and disrupting gut-liver axis in zebrafish - Yang Shu; Kaiwen Hu; Chenxin Gong; Yingying Yu; Conghui Shan; Xinrui Ge; Haibin Yu; Wei Shi; Guangxu Liu (Journal of Hazardous Materials, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Lewis acid-mediated choline chloride-glycerol deep eutectic solvent pretreatment for Goji berry branches: Enhancing enzymatic saccharification and high-value utilization of lignin - Bingxue Sun; Huaitao Jiang; Guan-Ping Jin; Shi-Kui Han; Bolin Liu; Xiaoli Ge; Xiaoyou Xiu; Biaode Yang (Biomass and Bioenergy, 2026)

Source apportionment and probabilistic health risk assessment of soil heavy metals in a high-background carbonate region of Southwest China - Ge Jin; Zhaoyu Zhou; Zeming Shi; Yafeng Zhang; Huan Deng; Zhangliang Shi (Environmental Geochemistry and Health, 2026)

Systematic evaluation reveals the dynamics and functions of horizontal gene transfer widespread in algae - Limin Jia; Liangwei Li; Qijin Ge; Yanchun You; Kai Han; Sibo Wang; Jianwei Chen; Dazhi Wang; Xin Liu; Yunyun Zhuang; Guangyi Fan; Chengcheng Shi (Marine Life Science & Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Engineering Mn-confined Fe0-carbon with isolated oxygen-containing groups breaks the bottleneck for concurrent self-driven Fenton degradation of antibiotics and heavy metals immobilization - Yujiang Huang; Dan Liu; Zhouyang Shi; Tong Hu; Huiwang Dai; Sicheng Pan; Wenjun Zhou; Fei Ge; Daohui Lin; Lizhong Zhu (Journal of Hazardous Materials, 2026)

Facile construction of ZnWO4/Ti3C2 MXene type-II heterojunctions via hydrothermal self-assembly: Toward efficient clean energy conversion and environmental remediation - Keren Shi; Xiaoyu Li; Qiaowei Xiao; Ziyan Wang; Wende Yi; Jianlin Ren; Shaoying Ge; Changyi Yang; Huiqin Yao (Fuel, 2026)

Achieving 99% selective photocatalytic conversion of CO2 to CH4 via built-in electric field guided S-scheme charge transfer in UiO-66/CuS heterojunction - Jia Shi; Xiaoqing Shi; Linping Li; Kezhen Lai; Yanping Qiu; Ning Li; Yangqin Gao; Lei Ge (Chemical Engineering Journal, 2026)

High performance solar interface evaporator based on high-absorbent alginate fiber/cellulose fiber blended textiles - Ruihao Ge; Hailing Shi; Bin Wang; Kui Liu; Yixuan Wang; Chunkai Shi; Shaolong Li; Fengyu Quan; Xing Tian (Chemical Engineering Journal, 2026)

Resilience of Dehalococcoides enables complete reductive dechlorination of trichloroethene to ethene under high PFOS stress - Fang Zhang; Runlei Ge; Chongwen Shi; Tao Long; Kun Yang; Guanghe Li; Lifeng Cao (ENGINEERING Environment, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Research on the Mechanism of Adhesion Force of Ship Icing Based on Ultrasonic Anti-Icing and De-Icing System - Jian Zhang; Shi Hua; Mengwei Ge; Daidai Huo; Yordan Garbatov; Baran Yeter; Bai-Qiao Chen (Journal of Marine Science and Engineering, 2026)
The ultrasonic anti-icing and de-icing system applies an electrical field to the ship’s surface to weaken the adhesion between the ice layer and the steel plates, while using ultrasonic vibration to generate longitudinal shear forces that break the remaining adhesion, thereby achieving effective de-icing. This study employs the control variable method to examine how different vibration frequencies and configurations of ultrasonic vibrators (“de-icing formations”) impact the adhesion characteristics of the ice layer covering the hull steel plates. Due to the lack of existing experimental instruments for measuring the adhesion force of ship icing, we designed an intelligent device to test the adhesion force between the ship and the ice layer. This device incorporates high-precision sensors and an advanced data acquisition system, enabling real-time measurement and recording of adhesion force data between icing and the hull steel plates. Using the newly developed JUST flat plate adhesion force testing system, this study evaluates how various distribution strategies of ultrasonic vibrators influence the ice adhesion force. Furthermore, the experiment investigates the de-icing efficiency of ultrasonic vibrators with the same number of but different “de-icing formations” and vibration frequencies under identical conditions of ice thickness, time, and excitation current, and provides a detailed analysis of the variation in ice adhesion force. These results clarify the mechanism by which the ultrasonic system manages the adhesion force of ship icing. This research not only introduces new ideas and methods for ship anti-icing and de-icing technology but also offers a scientific basis for enhancing navigation safety and operational efficiency in icy conditions.

ISPH Simulation of Non-Equilibrium Suspended Sediment Transport Using a Generalized Sediment Transport Equation - Sai Ge; Shaowu Li; Ye Liu; Yang Shi; Dong Wang; Tinghao Yang (Journal of Marine Science and Engineering, 2026)
Non-equilibrium suspended sediment transport is the most general state in engineering practice. Earlier analytical and numerical models for non-equilibrium suspended sediment transport were primarily designed for specific case studies and lack universal applicability. This work aims to develop a generalized two-dimensional (2D) numerical model based on the incompressible smoothed particle hydrodynamics (ISPH) approach for simulating non-equilibrium suspended sediment transport. The model integrates a generalized bottom boundary condition that accounts for both deposition velocity and equilibrium concentration. The impact of turbulence, as well as the hindered settling effect, is also included in the model. The efficacy of the model was assessed using results from analytical or semi-analytical models under 1D unsteady and 2D steady sediment transport modes, as well as from laboratory experiments for 2D unsteady sediment transport. This model reveals the physical mechanism of the hindered settling effect. The effect is most significant in the main suspension zone, where particles interact frequently. In the near-bottom zone, it is limited by physical constraints, and the settling velocity reaches its minimum. In the top zone, the effect is limited by the very low particle concentration, where particle interactions are negligible. The model also captures the different responses caused by different distributions of the turbulent viscosity coefficient and the bottom reference concentration.

An integrated metabolomic and transcriptomic analysis of quality changes in fresh Huangjing during storage at normal and low temperatures - Lei Jiang; Yuyang Shi; Lei Huo; Tingting Zhang; Lei Huang; Jingjing Liu; Yongxin Li; Wanying Ge; Jinping Si; Huqing Yang (Postharvest Biology and Technology, 2026)

Driving floc active site generation for enhanced low-molecular-weight organics removal in continuous dosing coagulation: The role of mixing conditions - Yukai Zong; Xin Jin; Shi Cheng; Li Liu; Shouqiang Huang; Dongdong Ge; Pengkang Jin (Journal of Water Process Engineering, 2026)

Ligand-specific tuning of an olfactory receptor to respond to sex pheromones in cowpea weevil, Callosobruchus maculatus - Hao-Ran Lu; Shan Li; Li-Jie Zhang; Kai Shi; Si-Qin Ge; Zhen Zou (Insect Biochemistry and Molecular Biology, 2026)

Geological sedimentary records constraining Earth-Moon system evolution over the past 60 million years: Insights from Cyclostratigraphy - Zhenwei Ge; Juye Shi; Quanyou Liu; Tailiang Fan; Zhiqian Gao; Huiyuan Xu; Ruyue Wang; Weihui Bi; Zhijun Jin (Gondwana Research, 2026)

Bidirectional shear-flow preparing lamellar graphene skeletons for tough and conductive nacre-like nanocomposites - Yicong Qin; Gangfeng Cai; Songhan Shi; Haodong Yang; Zihao Deng; Chendong Ge; Peng Li; Chao Gao; Zhen Xu (Chemical Engineering Journal, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

Ancient genomes reveal the origins and kinship organisation of Late Bronze Age populations in Northeastern China - Danyang Ge; Ruiqi Zou; Jiaqi Jin; Xiaoxuan Shi; Xiaoming Wang; Di Zhang; Xinghan Zhang; Quanchao Zhang; Chao Ning (Archaeological and Anthropological Sciences, 2026)

Heritable absolute DHA content enables selective breeding for enhanced n-3 LC-PUFA in common carp (Cyprinus carpio L.) - Xuesong Hu; Chitao Li; Xiaodan Shi; Dawei Zhong; Xiaona Jiang; Yanlong Ge; Xinyu Zhao; Xianhu Zheng; Zhiying Jia (Aquaculture, 2026)

Asynchronous Holocene moisture and precipitation variability in the Tibetan Plateau monsoon-westerlies transition zone - Tianlong Yan; Xiaomin Gao; Ge Shi; Chun Wang; Junjiang Dong; Qi Zhang; Xiaoru Zhang; Xiaoshuang Sun; Jinliang Liu; Can Zhang; Cheng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Seasonal dynamics of aqueous phase from hydrothermal carbonization of waste activated sludge: Unraveling composition, ecological risks, and resource opportunities - Tingting Yang; Ninghui Song; Xue Zhang; Yanqi Shi; Ping Li; Mingzhu Zhang; Feng Ge (Journal of Cleaner Production, 2026)

High-efficiency solar interface evaporator with vertical channels and hierarchical pores structure prepared from noodle wheat protein foam - Bin Wang; Chao Xu; Hao Liu; Hanxiao Shi; Hailing Shi; Ruihao Ge; Kui Liu; Yixuan Wang; Fengyu Quan; Xing Tian (Chemical Engineering Journal, 2026)

Enabling all-weather interfacial solar evaporation: A latent heat-regulated evaporator with Janus phase change microcapsules - Hailiang Ma; Xinwei Chen; Tiantian Yang; Yuhang Zhang; Linnan Zhang; Fanian Shi; Ge Xu; Jiangtao Fan; Fuxin Liang (Chemical Engineering Journal, 2026)

Interactions of carbon‑nitrogen coupling in the Agro-Pastoral Ecotone of Northern China - Shijun Tu; Wanfa Wang; Cai Li; Yuanbi Yi; Jinfeng Ge; Wenrui Yao; Wenhong Shi; Fu-Jun Yue; Zhongjun Wang; Yulin Qi; Si-Liang Li (CATENA, 2026)

MMD-Net: A Vision-Language Perception Model for Maritime Object Detection and Application - Bo Shi; Zitao Wang; Tianyu Cao; Hong Zhao; Qiqi Ge (Journal of Ocean University of China, 2026)

Effect of PET-MPs exposure on the toxicology of PCOS: a multi-platform computational toxicology investigation - Hai Bai; Yuxiao Jiang; Bozhi Zhu; Jing Huang; Yu Zhang; Xunrui Liu; Liying Ge; Shanshan Zhang; Yue Shi; Mingming Wang (Molecular Diversity, 2026)

Glutathione-Modified MoS2 Quantum Dots for Detection of Fe3+ and Ag+ ions in Water and Cell Imaging Applications - Yi Shi; Hongling Ge; Ge Li; Benhua Xu (Journal of Fluorescence, 2026)

Effect of Dry–Wet Cycling on the Abrasive Water Jet Cutting Performance of Green Sandstone - Zhaolong Ge; Zhuolin Shi; Qinglin Deng; Jianming Shangguan; Zhi Yao; Yuhuai Cui; Houhan Pu (Rock Mechanics and Rock Engineering, 2026)

A simple model for long-term prediction of sewage flow in a changing climate - Jingyu Ge; Jiuling Li; Ruihong Qiu; Tao Shi; Shuting Wang; Zi Huang; Zhiguo Yuan (Water Research, 2026)

Tributyl phosphate disrupts hepatic lipid metabolism via cGAS-STING signal pathway mediated inflammation - Liwei Yang; Zhili Ge; Xuehan Ding; Jingjing Shi; Jiaxin Zhang; Tianyou Wang; Huibin Jiang; Xinyu Zhang; Liting Zhou (Toxicology Letters, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Influence of DOM on Cd speciation during soil weathering in Permian strata: A case study in Xingwen County, Southern Sichuan Province, China - Ge Jin; Zeming Shi; Huan Deng; Tianliang Zheng; Yafeng Zhang; Jixiang Xie; Zhangliang Shi; Yinghai Zhu; Na Zhang; Chengjie Zou (Journal of Hazardous Materials, 2026)

Numerical simulation of refracturing fracture propagation behaviors under non-uniform pore pressure field for the waterflooded reservoir - Xian Shi; Xiaoxin Ge; Wanqiang Gu; Wei Liu; Qi Gao; Anhai Zhong; Liaoyuan Zhang; Tiankui Guo (Geomechanics for Energy and the Environment, 2026)

Development of high internal phase emulsion utilizing guar gum and soy lecithin as co-emulsifiers and its impact on the quality of chiffon cake as a fat substitute - Ge Shi; Jiahui Li; Yuqi Ma; Tian Xia; Chaomin Yin; Zhenshun Li (Food Hydrocolloids, 2026)

Bacterial cellulose/tea polyphenol films from tea waste via anaerobic synthesis: A sustainable material for active food preservation - Ge Gao; Haolong Zheng; Shaofang Niu; Yi Wang; Xueqing Zhao; Yucheng Shi; Liyuan Sun; Mingchang Li; Guoqiang Li; Ting Ma (Food Packaging and Shelf Life, 2026)

Revised modality-driven approach for enhanced analytical solutions to complex multi-mode coupled flutter: Influence of suspension bridge configurations - Jinbo Zhu; Yongxin Yang; Jinjie Zhang; Haojun Xu; Yaojun Ge; Rui Zhou; Yunliang Shi; Aihong Kang (Engineering Structures, 2026)

Study on Antioxidant Capacity and Apoptosis in Liver of Chicks Following in Ovo Feeding of Selenized Glucose and Methylselenised Glucose - Minmeng Zhao; Qiao Shi; Ruixin Su; Kang Wen; Jing Ge; Daoqing Gong; Yun Zheng (Biological Trace Element Research, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Attributing GHG emissions to individual facilities using multi-temporal hyperspectral images: Methodology and applications - Yichi Zhang; Ge Han; Yiyang Huang; Huayi Wang; Hongyuan Zhang; Zhipeng Pei; Yuanxue Pu; Haotian Luo; Jinchun Yi; Tianqi Shi; Siwei Li; Wei Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Co-fermentation of Hanseniaspora uvarum and Saccharomyces cerevisiae improves flavor in low-alcohol peach beverages - Haiyan Yu; Lei Shi; Chen Chen; Chang Ge; Xin Pan; Qian Chen; Huaixiang Tian (Food Research International, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

Plasma MicroRNA and Protein Signature Associated with Obesity in the Chinese Han Population Using MicroRNA Omics and Proteomics Analysis of 1026 Subjects - Yun-Xia Xie; Jian-Ge Qiu; Zhao-Hui Yang; Chen Ding; Le-Ming Shi; Si-Jia Wang; Li Jin; Bing-Hua Jiang (Phenomics, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

Distinct roles of nitrogen and phosphorus availability in preventing soil organic carbon loss in alfalfa-converted cropland - Xu-Long Zhang; Ge Li; Xiao-Peng Shi; Yang-Yang Zhao; Hai-Long Ma; Wen-Feng Cong; Fusuo Zhang; Feng-Min Li (Agriculture, Ecosystems & Environment, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Pharmaceuticals and personal care products in China’s aquatic environments: A decadal update (2013–2022) - Guosong Chang; Yonghao Huangfu; Yue Shi; Xinyue Shi; Shuai Cao; Yiting Ge; Ke An; Qingwei Bu; Gang Yu (Journal of Hazardous Materials, 2026)

Simultaneous denitrification and phosphorus removal accomplished by denitrifying biofilters assembled with innovative sulphur-fly ash ceramic carriers - Sijie Ge; Ge Chen; Limei Yuan; Jun Lv; Tongtong Shi; Chuanyi Zhang (Journal of Environmental Management, 2026)

Nondestructive assessment of refrigerated quality attributes of kiwifruit via hyperspectral imaging coupled with a point-to-interval prediction model - Sunli Cong; Jun Sun; Lei Shi; Chunxia Dai; Xiaohong Wu; Bing Zhang; Kunshan Yao; Xiao Ge (Food Chemistry, 2026)

Remediation of ternary heavy metal-polyethylene microplastics co-contaminated soil using co-modified biochar with deep eutectic solvent and warm patch: competitive interactions, mechanistic insights, and microbial community response - Luxin Zhang; Xiaobing Liu; Sishang Ge; Weiwei Shi; Rui Zhang; Chaoyang Li; Rong Chen (Environmental Research, 2026)

Polystyrene microplastics alter the toxicity of 6PPD to zebrafish (Danio rerio) larvae - Yuexing Zhao; Weitao Liu; Jianfeng Feng; Ning Gao; Jinzheng Liu; Ruiying Shi; Aurang Zeb; Jianling Wang; Qi Wang; Chuan Yin; Xinwei Shi; Xiang Li; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

High-performance ZnFe2O4: enabling efficient pollutant degradation and potent biofilm ablation with enhanced catalytic-antimicrobial activity - Xuechao Shi; Shuxian Hou; Shujie Li; Yao Xiao; Jun Ge; Yuhan Ji; Zhiru Tao; Yimei Wang; Wanzhen Li; Weiwei Zhang; Jun Wang; Zuchun Zhao; et al. (Chemical Engineering Journal, 2026)

Innovative NFC-based flexible sensing system for wireless and battery-free detection of H2S: A game-changer in real-time fresh food freshness evaluation - Ning Shi; Yan Tong; Boyang Xu; Xiaohu Ge; Yueqiang Cao; Yu Han; Yunda Chen; Anxin Luo; Xiaochan Wang; Gang Liu; Xiande Zhao; Guo Zhao (Chemical Engineering Journal, 2026)

Enhanced microalgal-bacterial granulation via a novel two-stage strategy: initial Microthrix parvicella-induced limited filamentous bulking and subsequent hydrodynamic-phototrophic synergy - Mengting Li; Zhipeng Chen; Zhaoming He; Sheng Yu; Weican Shi; Qian Bi; Xiang Li; Jiaqi Hu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2026)

Land subsidence and groundwater storage change from decadal InSAR measurements in southern Tangshan, China - Xuguo Shi; Yuan Jin; Daqing Ge; Wei Tang; Guijie Wang; Li Zhang; Shaocheng Zhang; Ling Zhang (Advances in Space Research, 2026)

HSPA8 promotes the progression of gastric cancer by activating the canonical Wnt pathway and glycolysis - Xiaoyi Shi; Peng Ge; Yalan Luo; Jianzhong Liu; Xiao Shi; Jingwen Zhang; Aixia Gong (Human Cell, 2025)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Electrokinetic remediation of hexavalent chromium-contaminated soil using low-molecular-weight organic acids combined with ion exchange membranes - Shuo Li; Jiao Yang; Qing Wang; Lieyan Shi; Pengxiang Liang; Yimin Hao; Wenjing Ge; Sviatoslav Viktorovich Fedorov; Hao Liu; Jingqing Gao (Journal of Water Process Engineering, 2025)

Earthworm intestine orchestrates dual host-microbiome detoxification of 6PPD-quinone - Ruiying Shi; Weitao Liu; Xinwei Shi; Xiang Li; Yichen Ge; Jinzheng Liu; Aurang Zeb; Yuexing Zhao; Yuebing Sun; Jing An (Journal of Hazardous Materials, 2025)

6PPD-Q driven rare and abundant taxa functional partitioning shapes soil ecological response - Xinwei Shi; Weitao Liu; Ruiying Shi; Yichen Ge; Xiang Li; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Dasong Lin; Yuebing Sun (Journal of Hazardous Materials, 2025)

Pelletization and steam reactivation of steel slag-derived calcium-based sorbent for CO2 capture - Nai Rong; Yuhan Wang; Zhihang Guo; Kaiwei Liu; Xiuliang Shi; Long Han; Lichao Ge; Geng Wang; Chao Hu; Xiaokang Wan (Journal of Environmental Chemical Engineering, 2025)

Smart Fe3O4-Zn NPs nanoplatforms: Integrated antibacterial activity, biofilm eradication, and magnetic propulsion for medical catheter blockage - Yuhan Ji; Xuechao Shi; Shuxian Hou; Jiaqin Huang; Jun Ge; Zhiru Tao; Xinxin Liu; Guanglei Feng; Shujie Li; Yao Xiao; Yimei Wang; Fei Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Foliar exposure to 6PPD-Q disturbs photosynthetic processes and induces oxidative stress in Eichhornia crassipes - Yichen Ge; Ruiying Shi; Weitao Liu; Xiang Li; Xinwei Shi; Aurang Zeb; Yuexing Zhao; Jing An; Yuebing Sun (Journal of Environmental Management, 2025)

Dual-functional carbon materials for sustainable Cr(VI)-organic co-decontamination: Structure activity relationship analysis of defect and oxygen content - Ming Zhang; Qingkai Shi; Jing Tong; Min Cheng; Hao Ge; Sai Li; Guangfu Wang; Li Du; Hongda Liu; Ao Chen; Zhongwu Li (Journal of Environmental Chemical Engineering, 2025)

Synergistic photothermal-magnetic nanoplatform: Recyclable TEG-SPIONs for ultra-efficient pathogen elimination in medical wastewater - Fei Ge; Yimei Wang; Jun Ge; Guoqiang Yang; Xinxin Liu; Shuxian Hou; Xuechao Shi; Yao Xiao; Shujie Li; Weiwei Zhang; Wanzhen Li; Ping Song; et al. (Journal of Environmental Chemical Engineering, 2025)

Engineering surface and subsurface oxygen vacancies of Ce Zr1-O2 solid solution for enhanced total toluene oxidation - Yang Yu; Mingjia Zhang; Huangang Shi; Jifa Qu; Yongheng Xiong; Wenyi Tan; Xinlei Ge; Qijie Jin (Journal of Environmental Sciences, 2025)

The 1907 Karatag earthquake doublet in Central Asia: Constraints from historic seismograms and surface rupture analysis - Xiao Yang; Xuhua Shi; Qi Ou; Hanlin Chen; Jin Ge; Feng Li; Mustafo Gadoev; Pulod Aminzoda; Jie Chen; Tao Li; Yangfan Huang (Global and Planetary Change, 2025)

A novel mannose-binding lectin homolog identified in the large yellow croaker (Larimichthys crocea) with evident binding and agglutinating activities - Yang Shu; Hengzhen Ye; Xinrui Ge; Kaiwen Hu; Chenxin Gong; Haibin Yu; Wei Shi; Guangxu Liu (Fish & Shellfish Immunology, 2025)

CO2-mediated selective cracking of n-butane to ethylene over HZSM-5-based catalysts - Zhongdong Zhang; Zhaoshuo Ge; Ruipu Wang; Yangping Lv; Enxi Wu; Chaowei Liu; Qin Wu; Daxin Shi; Kangcheng Chen; Guiyuan Jiang; Hansheng Li; Yaoyuan Zhang (Chemical Engineering Journal, 2025)

Effects on soil structures by root growth in the Loess Plateau, China - Rongqi Li; Hanruo Wang; Yilin Yan; Chao Han; Yulong Zhao; Yuanhao Liu; Shangyu Shi; Wenyan Ge; Fei Wang (CATENA, 2025)

In-situ visual delignification and cell-scale kinetics modeling using confocal Raman microscopy - Yuanping Huang; Zengling Yang; Chenjun Ge; Zhuolin Shi; Xinlei Wang; Lujia Han (Bioresource Technology, 2025)

Stigmasterol protects H9c2 cells from angiotensin-II induced hypertrophy by regulating apoptosis and autophagy - Mingming Chang; Jinjin Meng; Ge Liu; Chao Shi (Molecular & Cellular Toxicology, 2025)

Dose-dependent M2 macrophage polarization induced by Talaromyces marneffei promotes lung cancer cell growth via arginine-ornithine-cycle activation - Anqi Chen; Qian Yu; Leliang Zheng; Junqi Yi; Ziying Tang; Huabo Ge; Yue Ning; Na Yin; Yaohuan Xie; Shengnan Chen; Wenhua Shi; Xiaoling She; et al. (Medical Microbiology and Immunology, 2025)

Pollution profiles and human health risk assessment of BPA analogues in seafood from a Chinese coastal city - Yuehong Shen; Haonan Chen; Mengyuan Liang; Liguo Guo; Jie Gu; Lili Shi; Feng Ge; Guixiang Ji (Marine Pollution Bulletin, 2025)

Effects of miR-200b-3p and miR-424–5p regulating notch signaling pathway on atherosclerosis induced by PM2.5 in vitro - Tianyang Zhao; Xu Li; Zhili Ge; Jingjing Shi; Tianyou Wang; Jiaxin Zhang; Xinyu Zhang; Huibin Jiang; Liting Zhou; Lin Ye (Toxicology, 2025)

Research on mechanism of anti-icing of polar ships based on ultrasonic vibration - Shi Hua; Youxiang Wang; MengWei Ge; Jian Zhang (Ocean Engineering, 2025)

Decoding soil resilience: The role of eco-corona in alleviating toxicity for aged tire wear particles and benzalkonium chloride (C12) co-exposure - Bei Jiang; Yunhong Pu; Shengnan Shi; Zhaobo Chen; Dongxue Hu; Hui Ge; Shiming Cui; Yifan Wang; Pengcheng Zhang; Zihan Wang (Journal of Hazardous Materials, 2025)

Algal communities mediate hydroxylated polybrominated diphenyl ethers formation in mangrove surface sediments - Bin Li; Mengtao Zhang; Xueling Xiang; Jianghong Shi; Hui Ge (Journal of Hazardous Materials, 2025)

Association of ambient fine particulate matter (PM2.5) and its constituents with risk of pulmonary nodules in a lung cancer screening project - Xinyuan Ge; Ci Song; Chen Zhu; Yang Ding; Maojie Liu; Juan Yang; Chan Tian; Jiahao Zhang; Lili Wu; Lingying Zhu; Lei Shi; Xiangdong Cheng; et al. (Environmental Research, 2025)

Damaged mitochondria targeted copper doped carbon dots as a fluorescent probe hitchhike on circulated neutrophils for precise treatment of ischemic stroke - Ge Zhang; Yan Sun; Fang Li; Yong Liu; Mengdi Sun; Mingzhu Song; Ruizhen Lv; Jia Dong; Yijie Shi; Liang Zhao (Chemical Engineering Journal, 2025)

A hydrophobic and zincophilic protective layer for highly reversible Zn metal anodes - Chunyan Cao; Zhu Xu; Haoyang Li; Kexuan Wang; Ruiqing Li; Huibo Wang; Huilong Dong; Wei Zhang; Hui Liu; Shi Chen; Bin Fei; Mingzheng Ge (Chemical Engineering Journal, 2025)

Paraquat induced neuro-immunotoxicity: Dysregulated microglial antigen processing and mitochondrial activated mechanisms - Ge Shi; Kaidong Wang; Qi Liu; Chenyang Wu; Qianrong Zhang; Yuan Ma; Ai Qi; Min Huang (Chemico-Biological Interactions, 2025)

Potential effects of fertilization strategies on greenhouse gas emissions from bamboo forest soils - Ziliang Zhao; Dejin Dong; Yujie Zhao; Xuekun Cheng; Zixiang Weng; Qingyu Liu; Zhuonan Lou; Ke Wang; Ailing Ma; Wenting Ge; Hongyan Zhang; Yongjun Shi; et al. (Plant and Soil, 2025)

Examining the direct and indirect impacts of urbanization on vegetation net primary productivity across Chinese cities - Yulong Zhao; Hao Chen; Wenyan Ge; Shangyu Shi; Rongqi Li; Tamrat Sinore; Fei Wang (Agricultural and Forest Meteorology, 2025)

Study on the synergistic effect of pollution and carbon reduction and the emission reduction path of “Tailored Policy for Each Category”: evidence from the yellow river Basin, China - Wei Shi; Weijuan Wang; Wei Wei; Chengyuan Wang; Jun Ge; Runzhu Pei; Luyao Zhang (Air Quality, Atmosphere & Health, 2025)

The Identification and Synthesis of New Sea Cucumber Peptides Leveraging Peptidomics Technology, along with their Anti-Parkinson’s Disease Efficacy - Jiawei Liu; Yusheng Shi; Lingling Jin; Baixue Sun; Ruonan Wang; Guangbo Ge; Guanghao Zhu; Xiaolin Cui; Jie Zhao; Yan Zhang; Sheng Li (Journal of Neuroimmune Pharmacology, 2025)

Towards real-time weed detection and segmentation with lightweight CNN models on edge devices - Md Didarul Islam; Wenxin Liu; Pascal Izere; Puranjit Singh; Chong Yu; Benjamin Riggan; Kuan Zhang; Amit J. Jhala; Stevan Knezevic; Yufeng Ge; Santosh Pitla; Joe Luck; et al. (Computers and Electronics in Agriculture, 2025)

The role of endoplasmic reticulum stress in Atrazine-induced hepatic lipid accumulation - Honghao Qian; Shuping Ren; Haotang Zhao; Jingjing Shi; Zhili Ge; Jiaxin Zhang; Tianyou Wang; Xinyu Zhang; Huibin Jiang; Yuezhu Zhang; Lin Ye (Toxicology Letters, 2025)

Unraveling synergistic cascade inhibition of methane production in anaerobic digestion system by polyethylene microplastics and domestic sewage: Physical adsorption, metabolic disruption, and microbial community decoupling - Zhaoxuan Wang; Guoxu Ao; Yueqi Shi; Yuantong Liu; Kaiyu Wang; Minghui Yin; Xiyuan Sun; Jingping Ge; Hongzhi Ling; Shanshan Sun (Journal of Hazardous Materials, 2025)

SiO2 nanofiber and graphene oxide assisted fabrication of silica aerogels with novel interpenetration networks for efficient oil adsorption and photothermal evaporation - Meng-Jie Chang; Ge Bai; Jun Liu; Qiu-Yu Hu; Shu-Yi Hu; Yan Yin; Shi-Shun Cao (Journal of Environmental Chemical Engineering, 2025)

Asynchronous modes of paleofire occurrence in eastern monsoonal China since the LGM - Menglin Song; John Dodson; Scott Mooney; Ge Shi; Hong Yan (Global and Planetary Change, 2025)

CuO2 and tannic acid mediated synergistic antimicrobial and antifouling coatings - Qiang Liu; Chenqing Xu; Liqi Pang; Xi Xiong; Hao Zhou; Jinyang Zheng; Zhou Chen; Dongtao Ge; Wei Shi; Yanan Sun (Chemical Engineering Journal, 2025)

An ingenious structural design of NiCu-MOF bar-like nanosheet array: harnessing synergistic effects to attain exceptional ammonia oxidation performance - Guang-Lan Li; Yu-Hui Shi; Ri-Yang Huang; Tian-Ge Ma; Qian Zhuo; Ling Xu; Fei Jiang; Yu-Kun Zhai; Yong-Hou Xiao; Hong-Jiang Li; Yang Yan; Yun Zhao (Chemical Engineering Journal, 2025)

High-efficiency solar seawater evaporator by foam with hierarchically ordered channels based on carboxymethylated regenerated cellulose fibers - Hailing Shi; Ruihao Ge; Kai Li; Kui Liu; Yixuan Wang; Fengyu Quan; Kewei Zhang; Xing Tian (Carbohydrate Polymers, 2025)

Sources and potential health indicators in urban aerosols revealed by gas chromatography-mass spectrometry combined with nitrogen chemiluminescence detector: evidence from a megacity (Tianjin) of China - Jingying Ma; Yulin Qi; Yufu Han; Jinfeng Ge; Ling Wen; Xiaoli Fu; Wei Hu; Zongbo Shi; Dietrich A. Volmer; Pingqing Fu (Atmospheric Environment, 2025)

Multiscale adaptive fusion network for joint classification of hyperspectral and LiDAR data - Haizhu Pan; Weiwei Zhao; Haimiao Ge; Hui Yan; Cuiping Shi (International Journal of Remote Sensing, 2025)

Metabolomic alterations reveal toxic mechanisms of single and combined 6PPD and arsenic exposure on mung bean (Vigna radiata) - Sheharyar Khan; Aurang Zeb; Weitao Liu; Hamra Tariq; Abdul Mateen Baig; Hifza Iqbal; Ruiying Shi; Jinzheng Liu; Yuexing Zhao; Xiang Li; Yichen Ge (Journal of Hazardous Materials, 2025)

A 21-year of PM2.5-related premature mortality in China (2000–2020): spatial-temporal variations and health implications - Wen Wu; Yu Tian; Yusheng Shi; Jia Zhou; Yongliang Yang; Hao Yu; Zhitao Zhou; Jian Shi; Ge Qu; Yajun Wang (Journal of Cleaner Production, 2025)

Highly efficient orange-red multiple resonance hot exciton fluorescence emitters based on indolo[2,3-b]pyrazine derivatives - Bohong Liu; Zhizhi Li; Deli Li; Lin Wu; Tao Wang; Denghui Liu; Shi-Jian Su; Wei Li; Ziyi Ge (Chemical Engineering Journal, 2025)

Nitrifiers and denitrifiers under unconventional acidic/alkaline conditions: Nitrogen transformation, community shift, adaptive mechanisms - Weican Shi; Shuang Qiu; Zhaoming He; Yue Zhuo; Kerui Tang; Shijian Ge (Chemical Engineering Journal, 2025)

Tree thorns-inspired hyaluronic acid-based dissolving microneedles loaded with salvianolic acid B for effective hypertrophic scar treatment with enhanced long-term stability - Bricard Mbituyimana; Longjun Luo; Fuyu Qi; Yuchi Jiang; Omar Mohammad Atta; Mohamed S. Kishta; Mostafa Maboruk; Min Wu; Wei Ge; Zhijun Shi; Guang Yang (Carbohydrate Polymers, 2025)

2-Hydroxyanthraquinone induces cardiotoxicity in zebrafish via ferroptosis - Ziang Wang; Chenkai Ge; Wenbin Yuan; Wenwen Zha; Wanqing Chen; Weirong Li; Weitao Hu; Qinyuan Shen; Zhonghao Xiao; Xiaowen Shi; Huimin Li; Zigang Cao (Aquatic Toxicology, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Multiple Impacts of Climate Change and Anthropogenic Activities on Lacustrine Trophic State - Ge Xie; Yibo Zhang; Qing Wang; Kun Shi; Yunlin Zhang; Yongqiang Zhou; Boqiang Qin; Junliang He; Na Li (Global Change Biology, 2025)
The trophic state index (TSI) serves as a fundamental indicator for evaluating the water quality of lake ecosystems. Under climate change and human activities, global lake TSI has changed significantly, yet its response mechanisms remain unclear. To address this challenge, we developed a generalized TSI estimation model by integrating semi‐analytical algorithms with machine learning techniques, based on a comprehensive dataset comprising 3756 pairs of in situ measurements and remote sensing observations. The developed model demonstrated superior predictive performance with R 2 of 0.77 and RMSE of 8.25 for the testing dataset. Applying the model, we reconstructed a 21‐year time series (2003–2023) TSI for 14,189 global lakes with surface area ≥ 10 km 2 . The global mean TSI was estimated to be 54.07 ± 0.31. Among the lakes, 4.1% were classified as oligotrophic (TSI ≤ 38), 18.9% as mesotrophic (38 61). Globally, TSI showed a significantly increasing trend at a rate of 0.19 per decade ( p

Exploration of thermo-fluid-heat transfer evolution in salt cavern compressed air energy storage system under high-frequency injection and production conditions - Jun Huang; Xinbo Ge; Hongling Ma; Xilin Shi; Yinping Li; Chunhe Yang (Tunnelling and Underground Space Technology, 2025)

Atrazine exposure induces TDP-43 protein translocation: A potential mechanism for prefrontal cortical neurodegeneration induced by environmental pollutants - Yuan Ma; Kaidong Wang; Yuxuan Jiao; Yujing Li; Rong Hu; Yang Li; Ge Shi; Min Huang (Toxicology, 2025)

A mechanistic study of the efficient adsorption for platinum(IV) by amino-functionalized calix[4]arene - Tao Ge; Quan Shi; Liang Xu; Yifan Yang; Mengyang Li; Cheng Yang; Yongpan Tian; Zhuo Zhao (Science of The Total Environment, 2025)

Vascular-tissue-specific expression of an endo-1,4-β-xylanase enhances forage efficacy of sweet sorghum silage - Fengyong Ge; Huimin Wei; Wenzhe Zhang; Cuo Mei; Yihong Gao; Hanlei Yang; Xuekai Wang; Jingwen Cao; Zhuolin Liu; Jiayang Shi; Ran Xia; Kangxu Zhao; et al. (Molecular Plant, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

A comprehensive inventory of China's methane emissions: Insights and changes from 2010 to 2020 - Yusheng Shi; Yongliang Yang; Zhitao Zhou; Wen Wu; Ge Qu; Zhengqiang Li; Lei Huang; Tsuneo Matsunaga; Yasushi Yamaguchi; Shuying Zang; Miao Li (Journal of Cleaner Production, 2025)

Observing CO2 emissions from global key coal-fired power plants based on Orbiting carbon Observatory-3 satellite and improved Gaussian plume model - Zhitao Zhou; Yongliang Yang; Yusheng Shi; Yajun Wang; Wen Wu; Ge Qu (Journal of Cleaner Production, 2025)

Multiple competitive superiority made a great successful invasion of Spartina alterniflora in Eastern China: hints for management - Shi-Hua Li; Zhen-Ming Ge; Li-Shan Tan; Li-Na Xie; Ya-Lei Li (Journal of Environmental Management, 2025)

Use of stable isotopic signatures and fatty acid profiles to authenticate Chinese mitten crab (Eriocheir sinensis) reared in ponds and rice fields - Cui Han; Yujing Xiao; Zhongqi Dai; Lei Feng; Yan Shi; Xiaojie Liu; Jiachun Ge; Jiaxin Yang (Food Control, 2025)

Metal exposure is associated with cognitive function and plasma sTrem2 levels in coal miners: a cross-sectional study - Yang Li; Kaidong Wang; Ge Shi; Ai Qi; Yujing Li; Yuxuan Jiao; Rong Hu; Guilin Hu; Yonghang Li; Zhuoheng Shen; Min Huang (Environmental Research, 2025)

Sealing performance evaluation and analysis of the first salt caverns gas storage facility in the southwest plateau of China - Jun Huang; Xinbo Ge; Hongling Ma; Yinping Li; Xilin Shi; Zhixin Wang (Engineering Geology, 2025)

Development and operation of indigenous microalgal-bacterial consortium system treating eutrophic lake water: Consortium identification and system demonstration - Zhengshuai Wu; Weican Shi; Wenqi Yuan; Zhipeng Chen; Yue Xie; Zhe Lv; Jiajie Xu; Ayesha Algade Amadu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2025)

Mechanism of METTL14 regulates HBV-HCC malignant progression by mediating m6A modification of FOXP3 and thus transcriptional activation of ALDOB - Yu Fang; Xiaobin Shi; Jian Ge (Journal of Molecular Histology, 2025)

SOX4 promotes triple-negative breast cancer progression by promoting SRPX2 transcription to regulate AKR1C1 - Weiwei Ge; Chao Shi; Chun Ge; Siyun Zhang; Shuhua Chen; Jinfeng Qian (Journal of Molecular Histology, 2025)

Human Health Impact from Nonferrous Metal Mining: Exposure Risk with Hair as Biomarkers and the Associated Influencing Factors - Xueming Zheng; Feng He; Xiaoping Li; He Shen; Danqian Shi; Qishang Zhou; Shuang Zhang; Tunyang Geng; Yueheng Jiang; Pengyuan Jin; Xuelian Kui; Huimin Liu; et al. (Exposure and Health, 2025)

Neonicotinoid pesticides: residue detection and dietary risk assessment in commercially available plant-based agricultural products in North China - Peng Sun; Danqi Ren; Guotao Ding; Ning Hao; Ge Shi; Weihao Li (Environmental Monitoring and Assessment, 2025)

The SnRK1 kinase TaSnRK1.10 positively regulates heavy metal chromium tolerance mainly by mediating reactive oxygen species homeostasis and activating the phenylpropanoid biosynthetic pathway in wheat - Yihan Fu; Cong Chen; Pei Pei; Xiangyang Hao; Jiajia Jin; Shujie Shi; Qiang Ge; Pengfei Wang; Gezi Li; Guozhan Fu; Changqing Du; Guozhang Kang (Journal of Hazardous Materials, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

Cadmium exposure and health outcomes:An umbrella review of meta-analyses - Wenzhuo Xu; Sainan Wang; Wenhua Ruan; Mingyue Hao; Kele Jiang; Hao Guo; Anyi Geng; Mengting Man; Zheng Hu; Yun Liu; Guifang Jin; Haiyan Shi; et al. (Environmental Research, 2025)

Identification of Mood Disorders Causal Genes by Integrating the Brain Proteome and Transcriptome - Rong-kun Zhu; Hong-jian Zhou; Jun Shi; Ling Ge; Yi Lin; Wen-hao Yin; Hui Zeng; Xiong-wei Wang (Molecular Neurobiology, 2025)

Heat-triggered CRISPR/Cas12a microspheres for one-pot assays - Siying Xie; Shan Shao; Jin Wang; Jing Qu; Ying Cai; Xingyan Lai; Nan Min; Lidan Zhang; Yan Shi; Tingdong Li; Xiaomin Zhang; Bo Peng; et al. (Science Bulletin, 2025)

Dynamic and high methane emission flux in pond and lake aquaculture - Jiayu Zhao; Mi Zhang; Yini Pu; Lei Jia; Wei Xiao; Zhen Zhang; Pei Ge; Jie Shi; Qitao Xiao; Xuhui Lee (Journal of Hydrology, 2025)

TKSF-KAN: Transformer-enhanced oat yield modeling and transferability across major oat-producing regions in China using UAV multisource data - Pengpeng Zhang; Bing Lu; Jiali Shang; Changwei Tan; Qihan Xu; Lei Shi; Shujian Jin; Xingyu Wang; Yunfei Jiang; Yadong Yang; Huadong Zang; Junyong Ge; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Carboxymethyl cellulose/polyvinyl alcohol-based antioxidant film strengthened by physical/chemical bonding of cinnamaldehyde-tannin-metal nanoparticles - Chenkai Wang; Mengmeng Kang; Juan Xu; Yubo Xu; Xin Shi; Huihui Zhang; Yuchen Dong; Nuo Liu; Bingcheng Ge; Shuyan Gao (Food Chemistry, 2025)

Construction of a toxicity pathway from activation of the TLR4/NF-κB/NLRP3 axis to Parkinson's disease-like non-motor symptoms in mice - Kaidong Wang; Ge Shi; Yonghang Li; Qi Liu; Qianrong Zhang; Chenyang Wu; Yuxuan Jiao; Yuan Ma; Ai Qi; Min Huang (Environmental Toxicology and Pharmacology, 2025)

Root Diameter-Associated Exudates Drive the Changes in Rhizosphere Microbial communities - Huabo Du; Butian Wang; Muhammad Dawood; Peng Qu; Weifeng Li; Lingyan Zhang; Syed Asad Hussain Bukhari; Xuedong Shi; Meijun Qi; Shilang Dong; Yu Ge (Journal of Soil Science and Plant Nutrition, 2025)

Continuous organic mulching enhances the stability of soil organic carbon in Phyllostachys praecox: A 5-year in situ experiment - Yichen Zhang; Xiaomin Ge; Qiang Li; Shunyao Zhuang; Minmei Shi; Xingzhao Huang; Zhuangzhuang Qian (Soil Ecology Letters, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

A new in situ fracturing-enhanced oxidative remediation for various low-permeability phenanthrene-contaminated soils: Oxidation effectiveness and kinetics of potassium permanganate - Fu-Jiang Shi; Shi-Jin Feng; Jiu-Ge Niu; Qi-Teng Zheng; Xiao-Lei Zhang (Journal of Hazardous Materials, 2025)

Lead seasonality: Affect children’s blood lead levels and implication for lead exposure prevention - Jie Dong; Xiaoping Li; Yu Zhang; Xueming Zheng; Shuang Zhang; Qishang Zhou; Feng He; Danqian Shi; Yueheng Jiang; He Shen; Xu Zhang; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

Effect of different iron species on disinfection byproducts formation in drinking water distribution systems - Jining Ge; Yuan Zhuang; Yili Wang; Jiaqi Guo; Baoyou Shi (Chemical Engineering Journal, 2025)

Inheritance or Recruitment? The Assembly Mechanisms and Functional Dynamics of Microbial Communities in the Life Cycle of a Wood‐Feeding Beetle - Si‐Xun Ge; Yi‐Ming Niu; Li‐Li Ren; Shi‐Xiang Zong (Molecular Ecology, 2025)
Microbial partners enhance the metabolic capabilities of insects, enabling their adaptation to diverse ecological niches. Xylophagous insects have larvae that can digest lignocellulose and cope with plant secondary metabolites (PSMs). However, there is little information in terms of microbiome sources, dynamics and species contributions. This limits our understanding of the interaction between xylophagous insects and the microbiome. Monochamus saltuarius (Cerambycidae) is a significant borer of conifers. We used combined qPCR, host genomic and microbiome metagenomic datasets, as well as in vitro validation experiments to study the dynamics of the associated microbiome and its interactions with M. saltuarius . We evaluated microbial metabolic/biosynthetic contributions and validated their related functions. Our findings revealed that insect growth and development altered the quantity and community composition of associated bacteria and fungi. The egg microbiome was particularly susceptible to alteration due to oviposition pits. Bacterial transmission largely persisted between developmental stages, while fungal re‐acquisition primarily originated from the external environment. By reconstructing community pathway maps, we identified the cooperative interactions between the insect and its gut microbiome. As larvae transitioned from phloem to xylem feeding, the functional role of the gut microbiome in various pathways was weakened. Remarkably, high‐contribution bacterial species largely overlapped across different functional roles, and these species also showed considerable overlap between phloem and xylem feeding periods. Overall, our study highlights the unique interaction between xylophagous insects and their microbiome, which enhances their ability in lignocellulose digestion, PSMs degradation and the acquisition of essential amino acids, as well as vitamins.

Mitogenomic and Phylogenetic Analyses of Lysmata lipkei (Crustacea: Decapoda: Lysmatidae) - Xixi Zhang; Zhihuang Zhu; Jianxin Wang; Ge Shi; Qi Lin (Fishes, 2025)
This study aims to elucidate the characteristics of the mitogenome of Lysmata lipkei and investigate its phylogenetic relationships. Using both the Illumina NovaSeq 6000 (Illumina, Inc., San Diego, CA, USA) and PacBio Sequel II (Pacific Biosciences of California, Inc., Menlo Park, CA, USA) platforms, the complete mitogenome sequence of L. lipkei was determined. The mitogenome of L. lipkei was annotated, measuring 17,497 bp in length and comprising 13 protein-coding genes (PCGs), 2 ribosomal RNA genes (rRNAs), and 22 transfer RNA genes (tRNAs). The nucleotide composition of the genome exhibited an AT bias of 63.4%. Among the PCGs, the most frequently used codon was UUA. All tRNAs, except for trnD, which lacks the TψC loop, were capable of forming the typical cloverleaf structure. Phylogenetic trees for Caridea were constructed using Bayesian Inference (BI) and Maximum Likelihood (ML) methods based on the nucleotide sequences of the 13 PCGs. Both methods yielded consistent topological structures, with L. lipkei showing the closest phylogenetic relationship to L. kuekenthali. Additionally, Lysmatidae, Thoridae, and Hippolytidae formed a monophyletic clade. This research not only filled the gap in mitogenome data for Lysmatidae but also provided novel molecular insights into Caridean phylogenetics.

Revealing the Structure and Biodiversity Patterns of Fish Communities in River Networks Based on Environmental DNA - Ziyu Liu; Yongsheng Wu; Wenhui You; Shuxin Li; Ge Shi; Chen Zhang (Fishes, 2025)
Revealing taxonomic, functional, and phylogenetic dimensions of biodiversity is critical for the effective conservation and management of aquatic organisms in freshwater ecosystems subjected to multiple threats. Fish biodiversity patterns in river ecosystems exhibit complex spatiotemporal variation influenced by hydrological connectivity and the dispersal ability of species within the river network. This study utilized eDNA metabarcoding to investigate fish communities in three subtropical mountain rivers, aiming to uncover the community structure and spatiotemporal dynamics of the multidimensional biodiversity of fish communities across varying positions within the river network. The three biodiversity indices of the fish communities at the confluence were significantly greater than those of the mainstream community in the dry season, whereas the phylogenetic diversity of the fish community at the tributaries during the wet season was significantly greater than that in the mainstream. This likely reflected the unique spatial configuration of confluences and the seasonal dispersal of fish in the river network. The results of this study highlighted the important role of confluences and tributaries in river networks and the fact that they need to be prioritized to conserve riverine fish diversity.

An ODE-based swift and dynamic sewer airflow model - Tao Shi; Jiuling Li; Jingyu Ge; Shane Watts; Yaran Wang; Keshab Sharma; Zhiguo Yuan (Water Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Large-scale metabolomic landscape of edible maize reveals convergent changes in metabolite differentiation and facilitates its breeding improvement - Chunhui Li; Zhiyong Li; Baishan Lu; Yaxing Shi; Senlin Xiao; Hui Dong; Ruyang Zhang; Hui Liu; Yanyan Jiao; Li Xu; Aiguo Su; Xiaqing Wang; et al. (Molecular Plant, 2025)

Remediation effectiveness and mechanism on surfactant-enhanced remediation of low-permeability petroleum hydrocarbon contaminated soil under fracturing conditions - Shi-Jin Feng; Jiu-Ge Niu; Fu-Jiang Shi; Qi-Teng Zheng; Meng-Wen Gao (Journal of Hydrology, 2025)

Construction of ultra-light and flexible aerogels with superior high oil sorption capacity by controlling the mechanical property of SiO2 nanofibers - Meng-Jie Chang; Ge Bai; Jun Liu; Xin Li; Hui Wang; Shu-Yi Hu; Qiu-Yu Hu; Shi-Shun Cao; Jie Yang (Journal of Environmental Chemical Engineering, 2025)

Comparative study of Idesia polycarpa Maxim cake meal polysaccharides: Conventional versus innovative extraction methods and their impact on structural features, emulsifying, antiglycation, and hypoglycemic properties - Xin Shi; Xuemei Zhang; Lisha Wang; Yonghui Ge; Guangjing Chen (Food Chemistry, 2025)

Realizing continuous recycling of wasted LCO based on extractants functioning as H+ diffusion pump - Liang Lou; Junkai Xiong; Xinghua Guan; Liankang Ye; Houqiang Shi; Qihui Guo; Lvye Yang; Xiang Ge (Chemical Engineering Journal, 2025)

Dual redox-centered p(thiophene-TPA) conjugated polymers for high-performance flexible electrochromic supercapacitors - Xu Cheng; Chunhui Du; Jiaming Li; Yuqiao Zhang; Wenyuan Xu; Jianming Zhang; Hui Shi; Ge Zhang; Long Zhang (Chemical Engineering Journal, 2025)

Ultra broadband emission toward white LED based on dysprosium double perovskites CsxRb3-xDyCl6-xIx - Xue Bai; Zongqing Jin; Guanjun Xiao; Bo Zou; Qingqin Ge; Nannan Shi; Liwei Jiang; Cheng Sun; Tao Xiong; Yinan Zhang (Chemical Engineering Journal, 2025)

A Spatial Downscaling Approach for Enhanced Accuracy in High Wind Speed Estimation Using Hybrid Attention Transformer - Jieli Liu; Chunxiang Shi; Lingling Ge; Ruian Tie; Tao Zhou; Xiaojian Chen; Xiang Gu; Yue Wu; Zhanfei Shen (Journal of Meteorological Research, 2025)

Loss of protistan diversity weakens soil phosphorus availability - Zhechang Mei; Chuanfa Wu; Shengjing Shi; Haoqing Zhang; Zhenke Zhu; Jianping Chen; Tida Ge (Applied Soil Ecology, 2025)

CO2 emission from soil inorganic C in coastal croplands of the Yangtze Delta - Jun Cui; Ming Nie; Shuang Wang; Zhenke Zhu; Gongle Shi; Yakov Kuzyakov; Tida Ge (Agriculture, Ecosystems & Environment, 2025)

An innovative method and model for calculating the mountain tunnels with sprayed waterproofing membrane - Xiaohe Sun; Chenghua Shi; Zhu Peng; Guoqing Xiao; Yangyang Ge (Tunnelling and Underground Space Technology, 2025)

Analysis of the effect of highway extra-long tunnel Accompanying vehicle lighting on driving behavior in horizontal curve − A driving simulation study - Hongcheng Ge; Cancan Song; Difei Jing; Wei Li; Ze Shi; Zhongyin Guo; Fangyan Zhang (Tunnelling and Underground Space Technology, 2025)

Effects of environmental factors and genotype on performance, soil physicochemical properties and endophytic fungi of Salvia miltiorrhiza - Xin Zheng; Wenjing Chen; Xianen Li; Wenyi Shi; Xiang Sun; Qieyun Ge; Chao He; Xueli He (Rhizosphere, 2025)

Chronic sublethal exposure to chlorantraniliprole inhibits growth and development by disrupting the sugar and fatty acid metabolism in Spodoptera frugiperda - Xiao-Guang Liu; Qing-Ge Wang; Xiao-Ming Liu; Xiang Li; Meng-Fang Du; Cai-Hong Tian; Yun-Hui Zhang; Shi-Heng An (Pesticide Biochemistry and Physiology, 2025)

Antitussive drug dextromethorphan induces developmental impairment in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Zhi-Jie Lu; Jin-Ge Zhang; Li-Xin Hu; Zheng Huang; Si-Ying Li; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Reductive dechlorination of trichloroethene at concentrations approaching saturation by a Desulfitobacterium-containing community - Lifeng Cao; Runlei Ge; Chongwen Shi; Ziren Wan; Di Zheng; Wan Huang; Yixiao Wu; Kun Yang; Guanghe Li; Fang Zhang (Journal of Hazardous Materials, 2025)

Accumulation characteristics and fate modeling of phthalic acid esters in surface water from the Three Gorges Reservoir area, China - Shuai Sun; Bing Zhang; Junjie Hu; Wen Gu; Zhen Wang; Deling Fan; Feng Ge; Lili Shi; Lei Wang (Journal of Environmental Sciences, 2025)

A high-precision saltwater ice thickness and salinity detection method based on capacitive coupled planar microwave resonator - Han Shi; Mengjie Song; Junfeng Ge; Long Zhang; Xuan Zhang (Cold Regions Science and Technology, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Leakage Risk Analysis of Underground Gas Storage Salt Caverns with Micro-leakage Interlayer in Bedded Rock Salt of Jiangsu, China - Hongwu Yin; Hongling Ma; Xilin Shi; Xinbo Ge (Rock Mechanics and Rock Engineering, 2025)

Roles of ecological and hydrological processes in the variability of carbon fluxes in a salt marsh of the Yangtze Estuary: Model simulations vs. measurements - Ke-Hua Zhu; Zeng-Feng Li; Wei Zhao; Li-Ming Xue; Hua-Yu Chen; Qing Lyu; Shi-Xian Liu; Zhen-Ming Ge (Agricultural and Forest Meteorology, 2025)

Dry solidification of chloride salts and heavy metals in waste incineration fly ash by mayenite - Xin Li; Dongdong Ge; Nanwen Zhu; Yukai Zong; Shi Cheng; Pin Zhou; Min Jiang; Yun Gu; Shouqiang Huang (Waste Management, 2025)

Improving the mechanical properties of magnesium oxychloride cement by incorporating oyster shell powder - Zhi-hai He; Bin Wang; Jin-yan Shi; Xin-ge Wu; Hong-yu Tao; Ahmed Salah Jamal (Sustainable Chemistry and Pharmacy, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Mechanistic insight into the decomposition of sulfone compounds in supercritical water - Libo Lu; Wenwen Wei; Zijian Fang; Shi Liu; Zhiwei Ge; Hui Jin; Yunan Chen; Liejin Guo (Journal of Environmental Management, 2025)

Catalytic degradation of ethyl acetate at room temperature over Ni/NAC monolithic catalyst - Xiangci Wu; Chenglong Dai; Lisheng Zhang; Ge Gao; Jiahui Shi; Dan Zhao; Bingfeng Fu; Shejiang Liu; Jianfeng Fu; Hui Ding (Journal of Environmental Chemical Engineering, 2025)

Study on the effect of domesticated Escherichia coli on desulphurisation and spontaneous combustion oxidation characteristics of coals with varying sulphur contents - Xin Yi; Min Zhang; Jun Deng; Yang Xiao; Xinfu Shi; Long Ge (Fuel, 2025)

Stability of high-density lipoprotein-calcium ion complex stabilized high internal phase Pickering emulsions based on ion cross-linking - Yali Zhang; Ge Shi; Zhenshun Li (Food Research International, 2025)

Microbiota dynamics and metabolic mechanisms in fermented sausages inoculated with Lactiplantibacillus plantarum and Staphylococcus xylosus - Yulong Yang; Gang Zhou; Yining Ding; Wenjing Shi; Yueqian Chen; Chunbo Ge; Baocai Xu; Liu Yang (Food Research International, 2025)

Integrating Ni2P crystalline-NiFeBP amorphous heterojunction nanosheets on hierarchical nickel foam for superior overall water splitting - Guang-Lan Li; Fei Deng; Tian-Ge Ma; Yu-Hui Shi; Junyan Liu; Yang Yan; Qing Mao; Junjiang Bao (Chemical Engineering Journal, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

Anisotropic hydrogel sensors with muscle-like structures based on high-absorbent alginate fibers - Chen Hang; Zihan Guo; Kai Li; Jiuyong Yao; Hailing Shi; Ruihao Ge; Junxuan Liang; Fengyu Quan; Kewei Zhang; Xing Tian; Yanzhi Xia (Carbohydrate Polymers, 2025)

Devising optimized maize nitrogen stress indices in complex field conditions from UAV hyperspectral imagery - Jiating Li; Yufeng Ge; Laila A. Puntel; Derek M. Heeren; Geng Bai; Guillermo R. Balboa; John A. Gamon; Timothy J. Arkebauer; Yeyin Shi (Precision Agriculture, 2025)
Nitrogen Sufficiency Index (NSI) is an important nitrogen (N) stress indicator for precision N management. It is usually calculated using variables such as leaf chlorophyll meter readings (SPAD) and vegetation indices (VIs). However, no consensus has been reached on the most preferred variable. Additionally, conventional NSI (NSI uni ) calculation assumes N being the sole yield-limiting factor, neglecting other factors such as soil water variability. To tackle these issues, this study compared various variables for NSI calculation and evaluated two new N stress indicators in minimizing the impact of confounding water treatment. The following ground- and aerial-derived variables were compared for NSI uni calculation: SPAD, sampled leaf and canopy N content (LNC, CNC), LNC and CNC estimated using hyperspectral images acquired by an Unmanned Aerial Vehicle, and three VIs (Normalized Difference Vegetation Index (NDVI), Normalized Red Edge Index (NDRE), and Chlorophyll Index) from the hyperspectral images. Results demonstrated that ground-measured variables outperformed aerial-based variables in deriving N-responsive NSI. Especially, LNC derived NSI uni responded to N treatment significantly in ten out of thirteen site-date datasets. For the second objective, a modified NSI (NSI w ) and the NDRE/NDVI ratio were compared to NSI uni . NSI w reduced water treatment effects in over 80% of the datasets where NSI uni showed evident impacts. NDRE/NDVI performed similarly to NSI w , with the notable advantage of not requiring prior knowledge of soil water spatial distribution. This research pioneers the optimization of N stress indicators by identifying the best variables for NSI and mitigating the effects of soil water variability. These advancements significantly contribute to precision N management in complex field conditions.

Occurrence and ecological risks of organophosphate esters in the sediments of Hangzhou Bay and the East China Sea - Peng Zhang; Yaqing Cui; Ren Shi; Jing Wang; Linke Ge; Qinglin Mu (Marine Pollution Bulletin, 2025)

Response of nitrifiers to gradually increasing pH conditions in a membrane nitrification bioreactor: Microbial dynamics and alkali-resistant mechanism - Weican Shi; Zhaoming He; Jiahui Lu; Lingfeng Wang; Jianhua Guo; Shuang Qiu; Shijian Ge (Water Research, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Optimized acid leaching synthesis and steam regeneration of the steel slag-derived calcium-based sorbent for enhanced CO2 capture - Nai Rong; Xiuliang Shi; Shanshan Wang; Long Han; Kaiwei Liu; Lichao Ge; Yuhan Wang; Geng Wang (Journal of Cleaner Production, 2025)

Have human activities been accurately evaluated in sediment yield changes in the middle reaches of the Yellow River? - Yuanhao Liu; Fei Wang; Shuyu Zhang; Hanruo Wang; Chao han; Rongqi Li; Jianqiao Han; Wenyan Ge; Hao Chen; Shangyu Shi (Journal of Environmental Management, 2025)

Isolation and identification of novel hemp seed protein-derived pancreatic lipase inhibitory peptides - Zhenghai Zhang; Jingyi Ge; Lianhui Wei; Jie Shi; Yanru Ji; Xiangyu Xing; Yu Shi; Yan Dong (Food Bioscience, 2025)

Sulfation of hyperbranched β-glucan from mushroom Pleurotus tuber-regium enhances α-glucosidase inhibition and anti-glycation properties - Lei Chen; Peipei Ge; Tong Zeng; Lanlan Zhao; Ka-Hing Wong; Guiyang Shi; Peter C.K. Cheung; Zhongyang Ding (Food Bioscience, 2025)

Alleviating self-discharge of printed interdigital supercapacitor based on conjugatedly configured pairs of pre-sodiated manganese oxide - Liankang Ye; Liang Lou; Qihui Guo; Junkai Xiong; Houqiang Shi; Lvye Yang; Yuanyu Wang; Xucheng Liu; Ge Xiang (Chemical Engineering Journal, 2025)

Characteristics and Functions of Rhizosphere Bacterial Communities of Camelli sinensis cv. Shifocui with Cold Resistance Characteristics in Anhui Province, China - Shuiqin Shi; Enhui He; Junjie Ma; Mengrui Ge; Jiahui Gao; Tianyi Peng; Yu Fu; Jianfen Wang; Li Gong; Duoqi Zhou; Yafang Liu (Current Microbiology, 2025)

Association of ambient ozone exposure with early cardiovascular damage among general urban adults: A repeated-measures cohort study in China - Qiyou Tan; Min Zhou; Xiaojie You; Jixuan Ma; Zi Ye; Wendi Shi; Xiuqing Cui; Ge Mu; Linling Yu; Weihong Chen (Science of The Total Environment, 2024)

Impact of microplastics on plant physiology: A meta-analysis of dose, particle size, and crop type interactions in agricultural ecosystems - Xinwei Shi; Ruiying Shi; Xiuping Fu; Yuexing Zhao; Yichen Ge; Jinzheng Liu; Cuihong Chen; Weitao Liu (Science of The Total Environment, 2024)

Phytotoxicity of 6PPD and its uptake by Myriophyllum verticillatum: Oxidative stress and metabolic processes - Yuexing Zhao; Weitao Liu; Jinzheng Liu; Ruiying Shi; Aurang Zeb; Xiang Li; Yichen Ge (Science of The Total Environment, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Cadmium absorption and translocation in rice plants are influenced by lower air temperatures during grain filling stage - Xinzhen Zhang; Hang Xu; Jiangying Tang; Juan Yang; Zhiqiang Guo; Yang Xiao; Yulu Ge; Tian Liu; Qian Hu; Hejun Ao; Wanju Shi (Science of The Total Environment, 2024)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Response of Ceratophyllum demersum L. and its epiphytic biofilms to 6PPD and 6PPD-Q exposure: Based on metabolomics and microbial community analysis - Xiang Li; Weitao Liu; Yichen Ge; Ruiying Shi; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Qi Wang; Jianling Wang; Fan Mo; Aurang Zeb; Miao Yu (Journal of Hazardous Materials, 2024)

Impacts of plastic pollution on soil–plant properties and greenhouse gas emissions in wetlands: A meta-analysis - Wei Zhao; Zhen-Ming Ge; Ke-Hua Zhu; Qing Lyu; Shi-Xian Liu; Hua-Yu Chen; Zeng-Feng Li (Journal of Hazardous Materials, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Rational design of hierarchical defect-rich NiSe2/Se-NiCuOx heterostructures: Modulating electronic structure for exceptional ammonia oxidation performance - Guang-Lan Li; Tian-Ge Ma; Yu-Hui Shi; Fei Deng; Ri-Yang Huang; Yang Yan; Qing Mao; Yushan Li; Yonghou Xiao (Chemical Engineering Journal, 2024)

Highly efficient solar seawater evaporation by aerogel with vertical channels and hierarchical pores structure based on high-absorbent alginate fibers - Zihan Guo; Chen Hang; Kai Li; Jiuyong Yao; Hailing Shi; Ruihao Ge; Xiaole Gong; Fengyu Quan; Lijie Zhang; Kewei Zhang; Liwen Tan; Xing Tian; et al. (Chemical Engineering Journal, 2024)

Mangrove fungi in action: Novel bioremediation strategy for high-chloride wastewater - Zhiping Han; Edward S.X. Moh; Xin Ge; Xingqian Luo; Haizhou Wang; Jie Ma; Sien Shi; Jianzhi Ye (Bioresource Technology, 2024)

Tripartite-motif 3 represses ovarian cancer progression by downregulating lactate dehydrogenase A and inhibiting AKT signaling - Yu Cong; Xin Cui; Yaqian Shi; Xinxing Pan; Ke Huang; Zhe Geng; Pengfei Xu; Lili Ge; Jin Zhu; Juan Xu; Xuemei Jia (Molecular and Cellular Biochemistry, 2024)

Efficient RNA interference method by feeding in Brachionus plicatilis (Rotifera) - Yu Zhang; Dongqi Kan; Yang Zhou; Hairong Lian; Lingling Ge; Jing Shen; Zhongqi Dai; Yan Shi; Cui Han; Xiaojie Liu; Jiaxin Yang (Biotechnology Letters, 2024)

GB-SAR geocoding considering the radar attitude inclination angles for building facade deformation extraction - Peng Wang; Licheng Ge; Bin Zhang; Bo Shi; Hang Duan; Chuanfang Ke (International Journal of Remote Sensing, 2024)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Environmental concentrations of 6PPD and 6PPD-Q cause oxidative damage and alter metabolism in Eichhornia crassipes - Yichen Ge; Jinzheng Liu; Ruiying Shi; Xiang Li; Aurang Zeb; Qi Wang; Jianling Wang; Yuexing Zhao; Miao Yu; Chuan Yin; Hongxia Xiong; Weitao Liu (Science of The Total Environment, 2024)

Comparative toxic effect of tire wear particle-derived compounds 6PPD and 6PPD-quinone to Chlorella vulgaris - Jinzheng Liu; Miao Yu; Ruiying Shi; Yichen Ge; Jiantao Li; Aurang Zeb; Zhipeng Cheng; Weitao Liu (Science of The Total Environment, 2024)

Quantifying CO2 emissions of power plants with Aerosols and Carbon Dioxide Lidar onboard DQ-1 - Ge Han; Yiyang Huang; Tianqi Shi; Hongyuan Zhang; Siwei Li; Haowei Zhang; Weibiao Chen; Jiqiao Liu; Wei Gong (Remote Sensing of Environment, 2024)

Temperature changes of the Mid-Late Holocene transition in North China and their implications for regional cultural succession - Jiheng Shi; Shude Ren; Manyue Li; Can-Ge Li; Lili Song; Qinghai Xu; Shengrui Zhang (Quaternary Science Reviews, 2024)

Effects of Yellow Sea Warm Current on zooplankton community composition and functional groups in winter - Ruping Ge; Yiming Chen; Hongju Chen; Xueqing Zhang; Jie Shi; Haoran Li; Yunyun Zhuang; Guangxing Liu (Marine Environmental Research, 2024)

Analysis of canopy interception characteristics and influencing factors in typical artificial forest in the Loess Plateau semi-arid region - Yuanhao Liu; Fei Wang; Shuyu Zhang; Wenbin Ding; Rongqi Li; Jianqiao Han; Wenyan Ge; Hao Chen; Shangyu Shi (Journal of Environmental Management, 2024)

Undrained triaxial tests of underconsolidated overlying sediments of hydrate deposits in the South China Sea - Lei Wang; Wenqi Yu; Yang Ge; Shi Shen; Zhaoran Wu; Yiming Zhu; Yongchen Song; Yanghui Li (Gas Science and Engineering, 2024)

A novel macromolecular flame retardant based on sulfonyl diphenol monomer for simultaneous fire safety, transparency and high performance of thin-walled polycarbonate - Zongsheng Liu; Yi Zheng; Bangdong Ge; Meng Ma; Si Chen; Yanqin Shi; Huiwen He; Yulu Zhu; Xu Wang (Chemical Engineering Journal, 2024)

Improve the downscaling accuracy of high-resolution precipitation field using classification mask - Ruian Tie; Chunxiang Shi; Meng Li; Xiang Gu; Lingling Ge; Zhanfei Shen; Jieli Liu; Tao Zhou; Xiaojian Chen (Atmospheric Research, 2024)

Multi-scale analysis of the chemical and physical pollution evolution process from pre-co-pollution day to PM2.5 and O3 co-pollution day - Feng Wang; Chun Zhang; Yi Ge; Zhang Zhang; Guoliang Shi; Yinchang Feng (Science of The Total Environment, 2024)

Reduction in polycyclic aromatic hydrocarbon exposure in Beijing following China’s clean air actions - Yan Lin; Xiaodi Shi; Xinghua Qiu; Xing Jiang; Jinming Liu; Peiwen Zhong; Yihui Ge; Chi-Hong Tseng; Junfeng (Jim) Zhang; Tong Zhu; Jesus A Araujo; Yifang Zhu (Science Bulletin, 2024)

An automated approach for carbon integration in industrial park - Zhiwei Li; Ziting Ge; Chao Wang; Dawei Zhang; Dominic C.Y. Foo; Guangxin Liu; Lei Shi (Process Safety and Environmental Protection, 2024)

Atmospheric reactive nitrogen conversion kicks off the co-directional and contra-directional effects on PM2.5-O3 pollution - Feng Wang; Chun Zhang; Yi Ge; Ruiling Zhang; Bijie Huang; Guoliang Shi; Xiaoli Wang; Yinchang Feng (Journal of Hazardous Materials, 2024)

Upcycling of medical protective clothing for H2 production through catalytic steam reforming over Ni-impregnated catalysts - Kejie Wang; Jiajia Yu; Fangqi Liu; Jin Wang; Ge Kong; Guanyu Zhang; Suan Shi; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2024)

Impact of urban form on building energy consumption in different climate zones of China - Yiman Zhao; Xiaotian Ding; Ziyu Wu; Shi Yin; Yifan Fan; Jian Ge (Energy and Buildings, 2024)

Value-added resource recovery through forward osmosis promoted by pH-responsive biscarboxyimidazolium materials - Xiangfang Liu; Fengrong Qiu; Yan Yu; Yongqian Shi; Zhihong Zheng; Jingyun Zhang; Qingchun Ge (Desalination, 2024)

Etiological study on forest fire accidents using Bow-tie model and Bayesian network - Shi-yi Li; Xin Li; Fu-qiang Yang; Fan-liang Ge (Natural Hazards, 2024)

Adsorption behavior and mechanism of different types of (aged) microplastics for napropamide in soils - Qing Wang; Wenjie Ge; Renyong Shi; Jian He; Shuchang Li; Changqing Zhu; Xiaohui Zhang; Mali Shi; Ni Ni; Na Wang (Chemosphere, 2024)

Nonlinearly coupled electro-osmotic flow in variable charge soils - Xiaojuan Yang; Ge Shi; Chao Wu; Ye Yuan; Honglei Sun; Long Cang (Chemosphere, 2024)

A data-driven method for estimating sewer inflow and infiltration based on temperature and conductivity monitoring - Jingyu Ge; Jiuling Li; Ruihong Qiu; Tao Shi; Chenming Zhang; Zi Huang; Zhiguo Yuan (Water Research, 2024)

Multifunctional bacterial cellulose-bentonite@polyethylenimine composite membranes for enhanced water treatment: Sustainable dyes and metal ions adsorption and antibacterial properties - Xueqing Zhao; Mingbo Yang; Yucheng Shi; Liyuan Sun; Haolong Zheng; Mengmeng Wu; Ge Gao; Ting Ma; Guoqiang Li (Journal of Hazardous Materials, 2024)

Gasification characteristics and sulfur migration mechanism during supercritical water partial oxidation of 2-methylthiophene - Ruochen Xiong; Shi Liu; Jiayi Yu; Zhiwei Ge; Liejin Guo (Chemical Engineering Journal, 2024)

Lithium-Ion battery silicon Anodes: Surface engineering with novel additives for enhanced ion and electron transport - Kanghou Ma; Yitao He; Xinyue Zhao; Sunfa Wang; Ge Zhang; Chen Wang; Fangshuo Zhou; Wei Shi; Yaohui Zhang (Chemical Engineering Journal, 2024)

Dynamic behavior of electro-osmosis in variable charge soils: Insights on termination and direction reversal - Xiaojuan Yang; Ge Shi; Min Yang; Ye Yuan; Honglei Sun (Chemosphere, 2024)

Exploring the biosynthetic possibilities of hydroxylated polybrominated diphenyl ethers from bromophenols in Prorocentrum donghaiense: Implications for bioremediation - Bin Li; Jianghong Shi; Xueling Xiang; Mengtao Zhang; Hui Ge; Shuhan Sun (Chemosphere, 2024)

Deformation mechanisms of an existing pipeline due to progressively passive instability of tunnel face: Physical and numerical investigations - Jiangwei Shi; Yonghui Chen; Gangqiang Kong; Hu Lu; Ge Chen; Chao Shi (Tunnelling and Underground Space Technology, 2024)

Experimental investigation and cohesive zone modeling of the interface mechanical behavior in composite tunnel linings - Xiaohe Sun; Chenghua Shi; Yangyang Ge (Tunnelling and Underground Space Technology, 2024)

Comprehensive source identification of heavy metals in atmospheric particulate matter in a megacity: A case study of Hangzhou - Feili Li; Gaoxiang Zhang; Yifei Jinxu; Tianzheng Ding; Cong-Qiang Liu; Yunchao Lang; Nuohang Liu; Shuang Song; Yasheng Shi; Baozhu Ge (Journal of Environmental Management, 2024)

Biomass-MOF composites in wastewater treatment, air purification, and electromagnetic radiation adsorption – A review - Jinxuan Jiang; Yang Shi; Mingjun Wu; Mashallah Rezakazemi; Tejraj M. Aminabhavi; Runzhou Huang; Chong Jia; Shengbo Ge (Chemical Engineering Journal, 2024)

CT Angiography Radiomics Combining Traditional Risk Factors to Predict Brain Arteriovenous Malformation Rupture: a Machine Learning, Multicenter Study - Shaosen Zhang; Junjie Wang; Shengjun Sun; Qian Zhang; Yuanren Zhai; Xiaochen Wang; Peicong Ge; Zhiyong Shi; Dong Zhang (Translational Stroke Research, 2024)

Akkermansia muciniphila Protects Against Antibiotic-Associated Diarrhea in Mice - Shenyin Liu; Suying Zhao; Zhiwei Cheng; Yilin Ren; Xinyi Shi; Jing Mu; Xiangyang Ge; Yuan Dai; Lei Li; Zhan Zhang (Probiotics and Antimicrobial Proteins, 2024)

Dynamic variation of dissolved As, Sb, Fe and S in paddy soil triggered by nitrate loading to overlaying water - Zhao-Feng Yuan; Sha Zhang; Williamson Gustave; Tida Ge; Zhenke Zhu; Xiaoyu Shi; Xianjin Tang; Zheng Chen (Journal of Soils and Sediments, 2024)

Aerosol interference with open-path eddy covariance measurement in a lake environment - Lei Jia; Mi Zhang; Wei Xiao; Yini Pu; Zhen Zhang; Hengxin Bao; Pei Ge; Jie Shi; Yang He; Fuyu Yang; Kelly Aho; Peter Raymond; et al. (Agricultural and Forest Meteorology, 2024)

Phthalic acid esters: Are they a big concern for rivers flowing into reservoir with ecological facilities? - Huan-yu Tao; Jianghong Shi; Jiawei Zhang; Hui Ge; Xiaowei Liu; Xiao-yan Li (Water Research, 2024)

Timing and Kinematics of late Cenozoic Strike-slip Faults in the Western Tibetan Plateau: New Constraints from Provenance Analysis and Detrital Thermochronology - Xiaochun Wei; Hanlin Chen; Rong Yang; Ping Wang; Shanying Li; Xuhua Shi; Jin Ge (Tectonophysics, 2024)

Photosynthetic carbon allocation in native and invasive salt marshes undergoing hydrological change - Ya-Lei Li; Li-Na Xie; Shi-Hua Li; Dan Zhang; Zhen-Ming Ge (Science of The Total Environment, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Achieving carbon neutrality at single and multi-building complex levels – A review - Saeed Rayegan; Liangzhu (Leon) Wang; Radu Zmeureanu; Ali Katal; Mohammad Mortezazadeh; Travis Moore; Hua Ge; Michael Lacasse; Yurong Shi (Energy and Buildings, 2024)

A model coupling ecological and hydrodynamic processes for simulating the biogeomorphology of a coastal salt marsh - Ke-Hua Zhu; Jian Zeng; Zhen-Ming Ge; Yin Zuo; Shi-Hua Li; Lei-Hua Zhao; Yu Han; Hai-Feng Cheng; Pei Xin (Ecological Modelling, 2024)

Developmental toxicity and mechanism of dibutyl phthalate and alternative diisobutyl phthalate in the early life stages of zebrafish (Danio rerio) - Huan-Yu Tao; Jianghong Shi; Jiawei Zhang; Hui Ge; Mengtao Zhang; Xiao-Yan Li (Aquatic Toxicology, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Unveiling toxicity profile for food risk components: A manually curated toxicological databank of food-relevant chemicals - Xing-Xing Shi; Fan Wang; Zhi-Zheng Wang; Guang-Yi Huang; Min Li; Jesus Simal-Gandara; Ge-Fei Hao; Guang-Fu Yang (Critical Reviews in Food Science and Nutrition, 2024)

Preparation of white rot fungal inoculum and its application to bioremediation of chlorimuron-ethyl-contaminated soil - Xiangyu Shi; Xin Wang; Ling Ge; Wenrui Liu; Mengqin Yao; Jia Bao (Biotechnology Letters, 2024)

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

Endocrine toxicity of atrazine and its underlying mechanisms - Haotang Zhao; Honghao Qian; Jianwei Cui; Zhili Ge; Jingjing Shi; Yingchao Huo; Yuezhu Zhang; Lin Ye (Toxicology, 2024)

Toward soil carbon storage: The influence of parent material and vegetation on profile-scale microbial community structure and necromass accumulation - Yu-Zhu Li; Xue-Lian Bao; Shi-Xin Tang; Ke-Qing Xiao; Cheng-Jun Ge; Hong-Tu Xie; Hong-Bo He; Carsten W. Mueller; Chao Liang (Soil Biology and Biochemistry, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

The properties of plant-based protein particles with co-spray drying agents - Zhe Liu; Yanzheng Ge; Shanshan Li; Chao Wu; Xue Hei; Guangyue Ren; Benu Adhikari; Qiang Wang; Aimin Shi (Journal of Food Engineering, 2024)

Review of chemical looping technology for energy conservation and utilization: CO2 capture and energy cascade utilization - Jinbiao Yan; Sha Wang; Bin Hu; Huarong Zhang; Lipei Qiu; Weijun Liu; Yun Guo; Jun Shen; Bin Chen; Xiang Ge; Cong Shi (Journal of Environmental Chemical Engineering, 2024)

Self-sensing joints for in-situ structural health monitoring of composite pipes: A piezoresistive behavior-based method - Riwu Yao; Zhoutian Ge; Deyi Wang; Ningtao Shang; Jianfeng Shi (Engineering Structures, 2024)

Spatial-temporal-controlled NO gas and PARP1 siRNA delivery for alleviating the dilemma of deeper sonodynamic therapy in pancreatic cancer - Qingshuang Tang; Yuan Wang; Ruiqi Wu; Zexing Yu; Xue Shi; Yang Song; Lulu Zhang; Xin Li; Jinxia Zhang; Suhui Sun; Xiaotu Ma; Shuyu Xu; et al. (Chemical Engineering Journal, 2024)

Bioinspired wet adhesive carboxymethyl cellulose-based hydrogel with rapid shape adaptability and antioxidant activity for diabetic wound repair - Hongxia Xie; Ge Shi; Ruizi Wang; Xueyu Jiang; Qianqian Chen; Aixi Yu; Ang Lu (Carbohydrate Polymers, 2024)

The novel probiotic preparation based on Lactobacillus spp. mixture on the intestinal bacterial community structure of Cherry Valley duck - Shuiqin Shi; Mengrui Ge; Yan Xiong; Yixun Zhang; Wenhui Li; Zhimuzi Liu; Jianfen Wang; Enhui He; Liming Wang; Duoqi Zhou (World Journal of Microbiology and Biotechnology, 2024)

Phyllospheric Microorganisms and Bean Characteristics Influence Quality of Ten Genotypes of Coffea Arabica - Butian Wang; Xuedong Shi; Mengnan Shi; Meijun Qi; Zhenwei Zhang; Na Yang; Muhammad Dawood; Ahmad Naeem Shahzad; Yu Ge (Journal of Soil Science and Plant Nutrition, 2024)

Nitrogen fertilization enhances growth and development of Cacopsylla chinensis by modifying production of ferulic acid and amino acids in pears - Zifang Qin; Yang Ge; Wantong Jia; Liu Zhang; Mingyue Feng; Xinzheng Huang; Zhen Fu; Wangpeng Shi (Journal of Pest Science, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Efficient analysis of metabolites of industrial additives in cerebrospinal fluids - Ruihe Jin; Jun Shi; Jing Yang; Ge Yin; Chunjie Xia; Xiongwei Wang; Min Liu; Yan Wu (Environmental Chemistry Letters, 2024)

Expression characteristics and interference analysis of glucose-6-phosphate dehydrogenase reveal its importance in Pyropia yezoensis under salt stress - Li Huan; Mengmeng Shi; Guohong Lin; Baoyu Zhang; Xiujun Xie; Menglin Guo; Xi Qiang; Zhaojia Ge; Jianfeng Niu; Zhenbing Zheng; Xulei Wang; Guangce Wang (Algal Research, 2024)

The azole biocide climbazole induces oxidative stress, inflammation, and apoptosis in fish gut - Zhi-Jie Lu; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Xiao-Bing Long; Si-Ying Li; Fang-Zhou Gao; Qian-Qian Zhang; Guang-Guo Ying (Science of The Total Environment, 2024)

China's “coal-to-gas” policy had large impact on PM1.0 distribution during 2016–2019 - Tianqi Shi; Yanran Peng; Xin Ma; Ge Han; Haowei Zhang; Zhipeng Pei; Siwei Li; Huiqin Mao; Xingying Zhang; Wei Gong (Journal of Environmental Management, 2024)

Evaluation of styrene butadiene rubber asphalt modification mechanism and adhesion effect based on molecular simulation - Tangxin Xie; Zhongming He; Huanan Yu; Yuetan Ma; Changyun Shi; Chao Zhang; Jinguo Ge; Wan Dai (Fuel, 2024)

DEHP induces apoptosis and autophagy of the thyroid via Rap1 signaling pathway: In vivo and in vitro study - Xu Li; Honghao Qian; Hui Ye; Haotang Zhao; Jianwei Cui; Xiaoqi Fang; Zhili Ge; Jingjing Shi; Wen Qi; Lin Ye (Food and Chemical Toxicology, 2024)

Self-powered three-dimensional one-piece flexible pressure sensing system for human motion information aquisition - Lu Chen; Bao Shi; Wei Zhang; XinYing Liu; Ge Fang; LiXia Jia; RuoSi Yan (Chemical Engineering Journal, 2024)

Immunomodulatory melanin@Pt nanoparticle-reinforced adhesive hydrogels for healing diabetic oral ulcers - Erya Cai; Xiaoliang Qi; Yizuo Shi; Xinxin Ge; Yajing Xiang; Hangbin Xu; Ying Li; Yulong Lan; Jianliang Shen; Rongdang Hu; Hui Deng (Chemical Engineering Journal, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Single atom sites as CO scavenger to allow for crude hydrogen usage in PEMFC - Xian Wang; Xiaolong Yang; Ying Wang; Bingbao Mei; Zhao Jin; Yang Li; Zhaoping Shi; Zheng Jiang; Changpeng Liu; Wei Xing; Junjie Ge (Science Bulletin, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Different influences of La Niña types on the winter sub-seasonal Eurasian cold anomalies linked to Ural blocking - Binhe Luo; Yao Yao; Cunde Xiao; Dehai Luo; Ian Simmonds; Yina Diao; Wenqi Zhang; Yao Ge; Jiaqi Shi (Atmospheric Research, 2024)

STAT4-Mediated Klotho Up-Regulation Contributes to the Brain Ischemic Tolerance by Cerebral Ischemic Preconditioning via Inhibiting Neuronal Pyroptosis - Xi-Yun Liu; Ling-Yan Zhang; Xiao-Yu Wang; Shi-chao Li; Yu-Yan Hu; Jing-Ge Zhang; Xiao-Hui Xian; Wen-Bin Li; Min Zhang (Molecular Neurobiology, 2024)

The Role of Astrocytic Mitochondria in the Pathogenesis of Brain Ischemia - Ling-Yan Zhang; Yu-Yan Hu; Xi-Yun Liu; Xiao-Yu Wang; Shi-Chao Li; Jing-Ge Zhang; Xiao-Hui Xian; Wen-Bin Li; Min Zhang (Molecular Neurobiology, 2024)

Neurotransmitter norepinephrine regulates chromatosomes aggregation and the formation of blotches in coral trout Plectropomus leopardus - Nannan Zhao; Ke Jiang; Xiaoyu Ge; Jing Huang; Caiming Wu; Shi Xi Chen (Fish Physiology and Biochemistry, 2024)

Effects of New Psychoactive Substance Esketamine on Behaviors and Transcription of Genes in Dopamine and GABA Pathways in Zebrafish Larvae - Si-Ying Li; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Bulletin of Environmental Contamination and Toxicology, 2024)

Agarose amplification based sequencing characterization cell-free RNA in preimplantation spent embryo medium - Huajuan Shi; Qinyu Ge; Min Pan; Yuqi Sheng; Ting Qi; Ying Zhou; Yuqing Sun; Yunfei Bai; Lingbo Cai (Analytica Chimica Acta, 2024)

Heterogeneous reactions significantly contribute to the atmospheric formation of nitrated aromatic compounds during the haze episode in urban Beijing - Zhen Cheng; Xinghua Qiu; Ailin Li; Qianqian Chai; Xiaodi Shi; Yanli Ge; Theodore K. Koenig; Yan Zheng; Shiyi Chen; Min Hu; Chunxiang Ye; Rico K.Y. Cheung; et al. (Science of The Total Environment, 2024)

Review of waste plastics treatment and utilization: Efficient conversion and high value utilization - Bin Hu; Sha Wang; Jinbiao Yan; Huarong Zhang; Lipei Qiu; Weijun Liu; Yun Guo; Jun Shen; Bin Chen; Cong Shi; Xiang Ge (Process Safety and Environmental Protection, 2024)

Global sea level controlled the deep low-salinity pool evolution in the Japan sea since the last glacial period - Zhi Dong; Xuefa Shi; Jianjun Zou; Shizhu Wang; Chendong Ge; Yanguang Liu; Yonghua Wu; Ruxi Dou; Xinqing Zou (Quaternary Science Reviews, 2024)

Geomorphic expression of transverse drainages across the Tugerming anticline, southern Tian Shan: Implications for the river-fold interaction in the foreland - Feng Li; Xuhua Shi; Julien Charreau; Xiaogan Cheng; Rong Yang; Hanlin Chen; Jin Ge; Jinghan Wang (Journal of Structural Geology, 2024)

Nonvisual system-mediated body color change in fish reveals nonvisual function of Opsin 3 in skin - Zihao Zhang; Chenchen Shi; Jian Han; Xiaoyu Ge; Na Li; Yang Liu; Jing Huang; Shixi Chen (Journal of Photochemistry and Photobiology B: Biology, 2024)

An azole fungicide climbazole damages the gut-brain axis in the grass carp - Zhi-Jie Lu; Wen-Jun Shi; Fang-Zhou Gao; Dong-Dong Ma; Jin-Ge Zhang; Si-Ying Li; Xiao-Bing Long; Qian-Qian Zhang; Guang-Guo Ying (Journal of Hazardous Materials, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Visible-light Excited and Highly Photostable Organic Fluorophore with dual-state Emission - Yongchao Li; Liqing Zhang; Xianfeng Meng; Guowei Shi; Wei Gao; Guiyun Duan; Yanqing Ge (Journal of Fluorescence, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

How does the digital economy affect the provincial “zero-waste city” construction? Evidence from China - Meng-Ge Hao; Shi-Chun Xu; Xiao-Na Meng; Xiao-Fei Xue (Environmental Science and Pollution Research, 2024)

Catalytic gasification of anthracene in supercritical water with Ni/TiO2 catalyst: Products distribution and kinetics - Fanrui Meng; Shenghui Guo; Shi Liu; Changyifan Ren; Xingang Qi; Hui Jin; Zhiwei Ge; Liejin Guo (Fuel, 2024)

Extraction of eutrophic and green ponds from segmentation of high-resolution imagery based on the EAF-Unet algorithm - Yating Hu; Danyang Zheng; Shuqiong Shi; Yu Wang; Ge Liu; Kaishan Song; Dehua Mao; Shihong Wu; Liqiao Tian (Environmental Pollution, 2024)

Asiaticoside Attenuates Blood–Spinal Cord Barrier Disruption by Inhibiting Endoplasmic Reticulum Stress in Pericytes After Spinal Cord Injury - Zhenxin Hu; Tingting Wu; Ziheng Zhou; Yu Zhang; Qiyue Chen; Hanbing Yao; Mengchu Ji; Ge Shen; Chenling Dong; Chengge Shi; Zhixian Huang; Nizhou Jiang; et al. (Molecular Neurobiology, 2024)

Deriving aquatic PNECs of endocrine disruption effects for PFOS and PFOA by combining species sensitivity weighted distributions and adverse outcome pathway networks - Jiawei Zhang; Huanyu Tao; Jianghong Shi; Hui Ge; Bin Li; Yunhe Wang; Mengtao Zhang; Xiaoyan Li (Chemosphere, 2024)

Impacts of electric field-magnetic powder coupled membrane bioreactor on phenol wastewater treatment: Performance, synergistic mechanism, antibiotic resistance genes, and eco-environmental benefit evaluation - Bei Jiang; Qianzhi Zeng; Qiangwei Liu; Huiying Chai; Jinxun Xiang; Hongxin Li; Shengnan Shi; Aifu Yang; Zhaobo Chen; Yubo Cui; Dongxue Hu; Hui Ge; et al. (Science of The Total Environment, 2024)

Nitrogen rather than phosphorous addition alters the asymmetric responses of primary productivity to precipitation variability across a precipitation gradient on the northern Tibetan Plateau - Jialuo Yu; Ge Hou; Peili Shi; Ning Zong; Jinlong Peng (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Kinetic and mechanism of the reaction between Cl and several mono-methyl branched alkanes - Yan Chen; Weigang Wang; Junling Li; Li Zhou; Bo Shi; Cici Fan; Ke Wang; Hao Zhang; Hong Li; Maofa Ge (Journal of Environmental Sciences, 2024)

Utilizing adsorption of wood and its derivatives as an emerging strategy for the treatment of heavy metal-contaminated wastewater - Jinxuan Jiang; Yang Shi; Nyuk Ling Ma; Haoran Ye; Meenakshi Verma; Hui Suan Ng; Shengbo Ge (Environmental Pollution, 2024)

Longitudinal association of polycyclic aromatic hydrocarbons and genetic risk with lung function - Min Zhou; Shijie Yang; Limin Cao; Wencan Dai; Xiuquan Nie; Ge Mu; Xiaokang Zhang; Bin Wang; Jixuan Ma; Dongming Wang; Tingming Shi; Chaolong Wang; et al. (Environmental Pollution, 2024)

Nature-based solutions to mitigate early marsh-edge erosion in a coastal wetland - Ke Zhou; Shi-Xian Liu; Hai-Feng Cheng; Ke-Hua Zhu; Wei Zhang; Qing Lyu; Hua-Yu Chen; Pei Xin; Zhen-Ming Ge (Ecological Engineering, 2024)

Incorporating flexible sulfonate-imidazolium ion pair-functionalized MOF in cross-linked polyvinyl alcohol membrane for achieving superprotonic conduction - Ziyin Li; Yongnan Zhou; Jun Hu; Chao Shi; Shiwen Liu; Yuanyu Ge; Tianchi Zhou; Yingxiang Ye (Chemical Engineering Journal, 2024)

Mapping soil particle-size fractions based on compositional balances - Mo Zhang; Wenjiao Shi; Yuxin Ma; Yong Ge (CATENA, 2024)

Hierarchical and networked analysis of resilience factors in mountain communities in Southwest China - Yun-fei Zhao; Jian-min Cai; Lan Tang; Hai-bo Li; Shi-yu Hu; Hui-ge Xing (Natural Hazards, 2024)

A quantitative study on the characteristics of desiccation cracks and their effect on the shear failure characteristics of granite red soil - Yue Zhang; Yimin Huang; Zumei Wang; Menglu Shi; Jinshi Lin; Fangshi Jiang; Hongli Ge; Yanhe Huang (Bulletin of Engineering Geology and the Environment, 2024)

The evolution of the majiang paleoreservoir, west margin of xuefeng uplift: Insights from in situ calcite U–Pb dating and bitumen and shale trace element analysis - Xiang Ge; Chuanbo Shen; Yuqi Han; Yi Zhang; Guanzhong Shi; Zhenmin Cao; Guangyou Zhu (Marine and Petroleum Geology, 2023)

Study on semi-dynamic leaching and microstructure characteristics of MSWI fly ash solidified sediment - Xinmiao Shi; Haoqing Xu; Nan Zhang; Pengming Jiang; Aizhao Zhou; Yingying Zhao; Peng Ge (Journal of Environmental Management, 2023)

Ephedrine and cocaine cause developmental neurotoxicity and abnormal behavior in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

A Deep Learning Method for Statistical Downscaling of CLDAS Relative Humidity with Different Sources of Data: Sensitivity Analysis - Bin Bai; Chunxiang Shi; Ling Yang; Lingling Ge; Luhui Yue; Guangyu Liu (Journal of Meteorological Research, 2023)

Effect of hypoxia on the expression of microRNA in extracellular vesicles of human umbilical cord stem cells in vitro - Huifen Zang; Zhaohui Wang; Qingqing Wu; Lei Shi; Ge Chen (Cell and Tissue Banking, 2023)

Soil legacy nutrients contribute to the decreasing stoichiometric ratio of N and P loading from the Mississippi River Basin - Zihao Bian; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; Christopher Anderson; Wei‐Jun Cai; Charles S. Hopkinson; Dubravko Justic; Latif Kalin; Steven Lohrenz; Steven McNulty; et al. (Global Change Biology, 2023)
Human‐induced nitrogen–phosphorus (N, P) imbalance in terrestrial ecosystems can lead to disproportionate N and P loading to aquatic ecosystems, subsequently shifting the elemental ratio in estuaries and coastal oceans and impacting both the structure and functioning of aquatic ecosystems. The N:P ratio of nutrient loading to the Gulf of Mexico from the Mississippi River Basin increased before the late 1980s driven by the enhanced usage of N fertilizer over P fertilizer, whereafter the N:P loading ratio started to decrease although the N:P ratio of fertilizer application did not exhibit a similar trend. Here, we hypothesize that different release rates of soil legacy nutrients might contribute to the decreasing N:P loading ratio. Our study used a data‐model integration framework to evaluate N and P dynamics and the potential for long‐term accumulation or release of internal soil nutrient legacy stores to alter the ratio of N and P transported down the rivers. We show that the longer residence time of P in terrestrial ecosystems results in a much slower release of P to coastal oceans than N. If contemporary nutrient sources were reduced or suspended, P loading sustained by soil legacy P would decrease much slower than that of N, causing a decrease in the N and P loading ratio. The longer residence time of P in terrestrial ecosystems and the increasingly important role of soil legacy nutrients as a loading source may explain the decreasing N:P loading ratio in the Mississippi River Basin. Our study underscores a promising prospect for N loading control and the urgency to integrate soil P legacy into sustainable nutrient management strategies for aquatic ecosystem health and water security.

Dike risk evaluation incorporating the contribution of coastal wetlands: A case study on Chongming Island, China - Wei Zhang; Jian Zeng; Zhen-Ming Ge; Peng Yun; Ke-Hua Zhu; Ke Zhou; Shi-Xian Liu; Qing Lyu; Hua-Yu Chen (Ocean & Coastal Management, 2023)

Foliar application of selenium nanoparticles alleviates cadmium toxicity in maize (Zea mays L.) seedlings: Evidence on antioxidant, gene expression, and metabolomics analysis - Min Wang; Chunyi Mu; Yuliang Li; Yixuan Wang; Wenyan Ma; Chenghao Ge; Cheng Cheng; Gaoling Shi; Hongbo Li; Dongmei Zhou (Science of The Total Environment, 2023)

The Jinggangmycin-induced Mthl2 gene regulates the development and stress resistance in Nilaparvata lugens Stål (Hemiptera: Delphacidae) - Haowen Zhu; Sheraz Ahmad; Zhirou Duan; Junting Shi; Xingyu Tang; Qiaoqiao Dong; Chuanyuan Xi; Linquan Ge; Tao Wu; Yongan Tan (Pesticide Biochemistry and Physiology, 2023)

Distribution of mudsnail Bullacta caurina along smooth cordgrass Spartina alterniflora invasion stages on a coast of the Yellow Sea, China - Li Yang; Jingyi Shi; Rui Pan; Ruiping Yang; Hongshan Li; Shuang Wang; Baoming Ge (Marine Environmental Research, 2023)

Can digital-real integration promote industrial green transformation: Fresh evidence from China's industrial sector - Xiao-Na Meng; Shi-Chun Xu; Meng-Ge Hao (Journal of Cleaner Production, 2023)

Effects of plastic contamination on carbon fluxes in a subtropical coastal wetland of East China - Wei Zhao; Ke-Hua Zhu; Zhen-Ming Ge; Qing Lv; Shi-Xian Liu; Wei Zhang; Pei Xin (Journal of Environmental Management, 2023)

MnyCo3−yOx bimetallic oxide prepared by ultrasonic technology for significantly improved catalytic performance in the reduction of NOx with NH3 - Xiangbo Feng; Baorui Wang; Ge Gao; Shan Gao; Chong Xie; Jian-Wen Shi (Fuel, 2023)

Prussian blue analogues-derived zero valent iron to efficiently activate peroxymonosulfate for phenol degradation triggered via reactive oxygen species and high-valent iron-oxo complexes - Tong Wei; Xin-Sheng Zhu; Qi-Xue Wang; Ke-Ke Xu; Fu-Kai Tang; Ming-Zhu Zhang; Shi-Wen Lv; Feng Ge (Environmental Research, 2023)

Efficient singlet oxygen nanogenerator with low-spin iron for selective contaminant decontamination - Jingjing Jiang; Shu Niu; Shengda Liu; Hao Zhang; Yansong Liu; Tongze Sun; Donglong Shi; Bowen Zhao; Ge Yan; Mingxin Huo; Dandan Zhou; Shuangshi Dong (Chemical Engineering Journal, 2023)

Machine learning reveals the effects of drivers on PM2.5 and CO2 based on ensemble source apportionment method - Han Xu; Yi Ge; Chun Zhang; Zhenyu Wang; Bo Xu; Huan Zhao; Junbo Huang; Gen Wang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Research, 2023)

Chicken dendritic cell-targeting nanobodies mediated improved protective effects against H9N2 influenza virus challenge in a homologous sequential immunization study - Futing Jia; Chao Sun; Chongbo Ge; Zhannan Wang; Tongyu Zhang; Menglei Zhang; Wenfeng Wang; Yawen Tian; Yingkai He; Guilian Yang; Wentao Yang; Chunwei Shi; et al. (Veterinary Microbiology, 2023)

Degradation of levofloxacin from antibiotic wastewater by pulse electrochemical oxidation with BDD electrode - Tao Xu; Xiting Tang; Meiting Qiu; Xiaoliu Lv; Yang Shi; Yihui Zhou; Yanfei Xie; Mu. Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Shengbo Ge (Journal of Environmental Management, 2023)

Metagenomic analyses reveal microbial communities and functional differences between Daqu from seven provinces - Chutian Zhu; Yuxin Cheng; Qili Shi; Xiangyang Ge; Yong Yang; Yongguang Huang (Food Research International, 2023)

Corrigendum to “Decabromodiphenyl ether-induced PRKACA hypermethylation contributed to glycolipid metabolism disorder via regulating PKA/AMPK pathway in rat and L-02 cells” [Environ. Toxicol. Pharmacol., 2022, 90, 103808] - Yupeng Zhu; Li Jing; Xiangyang Li; Guiqing Zhou; Yue Zhang; Yujian Sang; Leqiang Gao; Sitong Liu; Zhixiong Shi; Zhiwei Sun; Wei Ge; Xianqing Zhou (Environmental Toxicology and Pharmacology, 2023)

Multi-scale domain and microstructure engineering for the high-energy-storage BCZT based lead-free relaxor ferroelectric ceramics - Jiayue Song; Fei Yan; Jinfeng Lin; Guanglong Ge; Cheng Shi; Jin Qian; Yali Hao; Yongqi Wei; Wu Yao (Chemical Engineering Journal, 2023)

Toward flame-retardant, transparency, and high mechanical property of polycarbonate based on low addition of linear polyborosiloxane - Zongsheng Liu; Meng Ma; Bangdong Ge; Yi Zheng; Si Chen; Yanqin Shi; Huiwen He; Yulu Zhu; Xu Wang (Chemical Engineering Journal, 2023)

Quinoxaline-based non-fullerene guest acceptor enables ternary organic solar cells achieving 18.9% efficiency via reducing energy loss and regulating morphology - Hui Liu; Zhenyu Chen; Ruixiang Peng; Yi Qiu; Jingyu Shi; Jintao Zhu; Yuanyuan Meng; Ziyan Tang; Jinna Zhang; Fei Chen; Ziyi Ge (Chemical Engineering Journal, 2023)

Climbazole causes cell apoptosis and lipidosis in the liver of grass carp - Zhi-Jie Lu; Wen-Jun Shi; Fang-Zhou Gao; Dong-Dong Ma; Jin-Ge Zhang; Si-Ying Li; Xiao-Bing Long; Qian-Qian Zhang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Modeling and optimization of synergistic ozone-ultraviolet-chlorine process for reclaimed water disinfection: From laboratory tests to software simulation - Ke-Fan Cao; Zhuo Chen; Yi-Ge Sun; Bang-Hao Huang; Qi Shi; Yu Mao; Yin-Hu Wu; Yun Lu; Hong-Ying Hu (Water Research, 2023)

Impacts of land-use change on carbon dynamics in China's coastal wetlands - Li-Shan Tan; Zhen-Ming Ge; Shi-Hua Li; Ke Zhou; Derrick Y.F. Lai; Stijn Temmerman; Zhi-Jun Dai (Science of The Total Environment, 2023)

Improving quantification of methane point source emissions from imaging spectroscopy - Zhipeng Pei; Ge Han; Huiqin Mao; Cuihong Chen; Tianqi Shi; Keyi Yang; Xin Ma; Wei Gong (Remote Sensing of Environment, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

A XCO Retrieval Algorithm Coupled Spatial Correlation for the Aerosol and Carbon Detection Lidar - Zhipeng Pei; Ge Han; Tianqi Shi; Xin Ma; Wei Gong (Atmospheric Environment, 2023)

Genome-wide identification and analysis of MIKC-type MADS-box genes expression in Chimonanthus salicifolius - Fang-Fang Gui; Ge-Ge Jiang; Bin Dong; Shi-Wei Zhong; Zheng Xiao; Qiu Fang; Yi-Guang Wang; Li-Yuan Yang; Hongbo Zhao (Genes & Genomics, 2023)

Multi-year nitrogen accumulation weakens the stabilizing effect of species asynchrony on drought resistance in a Tibetan alpine meadow - Ge Hou; Tiancai Zhou; Peili Shi; Jian Sun; Ning Zong; Jialuo Yu; Minghua Song (Agricultural and Forest Meteorology, 2023)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Enhancing wuyiencin productivity of Streptomyces albulus (CK15) by mutagenesis breeding with atmospheric and room temperature plasma - Yu Wah Thein; Liming Shi; Binghua Liu; Qiuhe Wei; Kecheng Zhang; Beibei Ge (World Journal of Microbiology and Biotechnology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Unraveling the in vivo biological fate of mPEG2000-PDLLA2500-COOH diblock copolymers by LC-MS/MS based on CID in source technique - Meiyun Shi; Xinyue Zheng; Hui Jiang; Yuncheng Ge; Ning Zhang; Xujian Duan; Yajun Liu; Hongyu Xue; Jiansong You; Lei Yin (Analytica Chimica Acta, 2023)

The Effect of Salinity on the Strength Behavior of Hydrate-Bearing Sands - Shi Shen; Lei Wang; Yang Ge; Jiawei Chu; Huiyong Liang (Journal of Marine Science and Engineering, 2023)
The first prerequisite for the efficient and safe exploitation of gas hydrate resources is to accurately analyze the primary mechanical performance of hydrate-bearing sediments (HBSs). The mechanical performance of HBSs is complex and affected by many factors, including the reservoir environment in situ (temperature, pore pressure, salinity). Several published studies have demonstrated a correlation of the mechanical behavior of hydrates with temperature and pressure (T-PP). However, the research on the effect of salinity on the mechanical properties of hydrates or HBSs is still a relatively blank field. This study found that the strength of HBSs decreased with increasing salinity. This phenomenon can be attributed to the influence of salinity on the phase equilibrium state of hydrates. NaCl changed the relationship between the phase equilibrium curve of the hydrate and the T-PP conditions. The distance between the T-PP conditions and equilibrium curve was reduced with increasing salinity, which in turn led to a decline in sample strength. Moreover, the effect of the phase equilibrium of hydrates on the mechanical performance of HBSs was further explored. NaCl was added to HBSs to regulate the phase equilibrium state of the hydrate. When the T-PP conditions were on the phase equilibrium curve, the strength behaviors of HBSs showed a high degree of consistency.

The impacts of COVID-19 on the cruise industry based on an empirical study in China - Jingen Zhou; Shu-Ling Peggy Chen; Wenming Wendy Shi; Maneerat Kanrak; Jiawei Ge (Marine Policy, 2023)

Leydig cell development in pubertal male rats is blocked by perfluorotetradecanoic acid through decreasing AMPK-mTOR-autophagy pathway - Yunbing Tang; Lei Shi; Shaowei Wang; Han Lu; Huitao Li; Jieqiang Lv; Ren-shan Ge; Yingfen Ying (Toxicology Letters, 2023)

Dissolved‑selenium removal using magnetic nanoparticles: A state-of-the-art review - Gang Chen; Feiyin Ge; Yao Wang; Pei Liu; Shuai He; Hao Shi; Zhongbiao Tan (Journal of Water Process Engineering, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

Distribution pattern of planktonic and benthic foraminifera in surface sediments near the equatorial western Indian Ocean and its indications of paleo-environment and productivity - Wei Shen; Shuqing Qiao; Rongtao Sun; Zhoutian He; Bin Wu; Lina Jin; Liang Chen; Zhengxin Yin; Chendong Ge; Xuefa Shi; Jie Sheng (Journal of Asian Earth Sciences, 2023)

Exogenous hydrogen sulphide alleviates nodule senescence in Glycine max-Sinorhizobium fredii symbiotic system - Juan Chen; Wu-Yu Liu; Xin Zhang; Qing Pan; Feng-Shuya Wang; Shi-Ming Wen; Jian-Hua Zhang; Ge-Hong Wei (Plant and Soil, 2023)

DUSP2 Deletion Inhibits Macrophage Migration by Inhibiting ERK Activation in Zebrafish - Yu-Jiao Li; Xin-Liang Wang; Ling-Yu Shi; Zong-Yi Wang; Zi-Ang Zhao; Shu-Chao Ge; Bing Hu (Fishes, 2023)
Dual-specificity phosphatase 2 (DUSP2) regulates the activation of members of the mitogen-activated protein kinase (MAPK) family, which is involved in a variety of cellular processes including cell proliferation, differentiation, apoptosis, and migration. DUSP2 also regulates the expression of inflammatory mediators in macrophages; however, it remains unknown whether DUSP2 participates in macrophage migration. Here, using the tail fin injury model in zebrafish larvae, we found that the deletion of DUSP2 inhibited the expression of pro-inflammatory cytokines and macrophage chemokines. Moreover, live imaging results showed that the migration of macrophages to the injury site was inhibited after DUSP2 deletion. This inhibitory effect was mediated through the reduced activation of extracellular regulated protein kinases (ERK) in DUSP2 knockout zebrafish.

Organophosphate esters in the seawater of the Bohai Sea: Environmental occurrence, sources and ecological risks - Rongguang Xing; Peng Zhang; Nan Zheng; Hao Ji; Ren Shi; Linke Ge; Hongrui Ma (Marine Pollution Bulletin, 2023)

Genome-wide identification, classification and expression analysis of the JmjC domain-containing histone demethylase gene family in Moso bamboo (Phyllostachys edulis) - Weijia Shi; Zhe Li; Kuo Dong; Bohao Ge; Cunfu Lu; Yuzhen Chen (South African Journal of Botany, 2023)

Experimental investigation on flame stability and emissions of lean premixed methane–air combustion in a developed divergent porous burner - Yang Liu; Yangbo Deng; Junrui Shi; Yongqi Liu; Xiaolong Wang; Bingquan Ge; Zhenyu Min (Journal of Cleaner Production, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Small RNA Profiling Reveals a Role of miRNAs in Response to Ralstonia solanacearum Infection in Tomato - Jianlei Shi; Wenshan Zai; Zili Xiong; Kelei Wang; Deju Shui; Zan’ge Jing (Journal of Plant Growth Regulation, 2023)

Assessment of heavy metal contamination of an electrolytic manganese metal industrial estate in northern China from an integrated chemical and magnetic investigation - Jiawei Zhang; Huanyu Tao; Hui Ge; Jianghong Shi; Mengtao Zhang; Zonglin Xu; Ruijie Xiao; Xiaoyan Li (Environmental Geochemistry and Health, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

An insight into direct water injection applied on the hydrogen-enriched rotary engine - Cheng Shi; Sen Chai; Huaiyu Wang; Changwei Ji; Yunshan Ge; Liming Di (Fuel, 2023)

Halogen atoms determine the inhibitory potency of halogenated bisphenol A derivatives on human and rat placental 11β-hydroxysteroid dehydrogenase 2 - Lei Shi; Bingru Zhang; Yingfen Ying; Yunbing Tang; Shaowei Wang; Yang Zhu; Huitao Li; Ren-shan Ge; Yi Liu (Food and Chemical Toxicology, 2023)

Study on refined mathematical model of solar chimney power plant integrated with seawater desalination and the influence of dewing - Lu Zuo; Long Huang; Pengzhan Dai; Yu Chen; Shi Chen; Yunting Ge (Desalination, 2023)

Highly enhanced energy storage performance of trilayered gradient polymer-based nanocomposite via 2D SNO@Ag nanosheets - Hairui Bai; Guanglong Ge; Fei Yan; Kun Zhu; Jin Qian; Cheng Shi; Yanxia Li; Haijiao Xie; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Facilitating the proton conductivity of polyvinyl alcohol based proton exchange membrane by phytic acid encapsulated Zn-azolate MOF - Yongnan Zhou; Shiwen Liu; Xiaosai Hu; Yuanyu Ge; Chao Shi; Huanling Wu; Tianchi Zhou; Ziyin Li; Jinli Qiao (Process Safety and Environmental Protection, 2023)

Using environmentally friendly technology for fabricating special plywood with ultra-high strength - Shida Zuo; Yunyi Liang; Yingji Wu; Shengbo Ge; Jiangtao Shi; Xinxin Ma; Liping Cai; Jianzhang Li; Su Shiung Lam; Changlei Xia (Journal of Cleaner Production, 2023)

Gasification integrated with steam co-reforming of agricultural waste biomass over its derived CO2/O2/steam-mediated porous biochar for boosting H2-rich syngas production - Xuesong Zhang; Ge Kong; Xin Zhang; Kejie Wang; Quan Liu; Suan Shi; Lujia Han (Journal of Environmental Chemical Engineering, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Deciphering the fate of osmotic stress priming on enhanced microorganism acclimation for purified terephthalic acid wastewater treatment with high salinity and organic load - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Bioresource Technology, 2023)

Effective Removal of Aqueous Cu(II) Pollution by a Novel Readily Prepared Porous Biomaterial Using Crab Shell Wastes - Ya-Ming Ge; Liang Zhang; Yong Zhang; Jia-Shun Yang; Hui-Min Gao; Shi-Jie Li; Jun-Zhi Liu (Water, Air, & Soil Pollution, 2023)

OsCYBDOMG1, a cytochrome b561 domain-containing protein, regulates salt tolerance and grain yield in rice - Ping Deng; Chengjuan Cao; Xingyu Shi; Qun Jiang; Jinjin Ge; Like Shen; Chunxia Guo; Ling Jiang; Wen Jing; Wenhua Zhang (Theoretical and Applied Genetics, 2023)

A Spacetime Odyssey of Neural Progenitors to Generate Neuronal Diversity - Mengmeng Ge; Amirhossein Sheikhshahrokh; Xiang Shi; Yu-Hong Zhang; Zhiheng Xu; Qing-Feng Wu (Neuroscience Bulletin, 2023)
To understand how the nervous system develops from a small pool of progenitors during early embryonic development, it is fundamentally important to identify the diversity of neuronal subtypes, decode the origin of neuronal diversity, and uncover the principles governing neuronal specification across different regions. Recent single-cell analyses have systematically identified neuronal diversity at unprecedented scale and speed, leaving the deconstruction of spatiotemporal mechanisms for generating neuronal diversity an imperative and paramount challenge. In this review, we highlight three distinct strategies deployed by neural progenitors to produce diverse neuronal subtypes, including predetermined, stochastic, and cascade diversifying models, and elaborate how these strategies are implemented in distinct regions such as the neocortex, spinal cord, retina, and hypothalamus. Importantly, the identity of neural progenitors is defined by their spatial position and temporal patterning factors, and each type of progenitor cell gives rise to distinguishable cohorts of neuronal subtypes. Microenvironmental cues, spontaneous activity, and connectional pattern further reshape and diversify the fate of unspecialized neurons in particular regions. The illumination of how neuronal diversity is generated will pave the way for producing specific brain organoids to model human disease and desired neuronal subtypes for cell therapy, as well as understanding the organization of functional neural circuits and the evolution of the nervous system.

Effects of Selenoprotein S Knockdown on Endoplasmic Reticulum Stress in ATDC5 Cells and Gene Expression Profiles in Hypertrophic Chondrocytes - Hui Wang; Zhengzheng Li; Yinan Liu; Meng Zhang; Yawen Shi; Ying Zhang; Ge Mi; Mengying Wang; Ying He; Yonghui Chen; Chen Chen; Jinghong Chen (Biological Trace Element Research, 2023)

Random walk multipath method for Galileo real-time phase multipath mitigation - Mingxian Hu; Yibin Yao; Maorong Ge; Frank Neitzel; Junbo Shi; Peifen Pan; Meihao Yang (GPS Solutions, 2023)

Improved chlorophyll and water content estimations at leaf level with a hybrid radiative transfer and machine learning model - Jiating Li; Nuwan K Wijewardane; Yufeng Ge; Yeyin Shi (Computers and Electronics in Agriculture, 2023)

Uncovering drivers of community-level house price dynamics through multiscale geographically weighted regression: A case study of Wuhan, China - Binbin Lu; Yong Ge; Yilin Shi; Jianghua Zheng; Paul Harris (Spatial Statistics, 2023)

A continuous paleorecord of vegetation and environmental change from Erxianyan Wetland over the past 60,000 years in central China - Menglin Song; John Dodson; Fengyan Lu; Ge Shi; Hong Yan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Visualization study on combustion characteristics of direct-injected hydrous methanol ignited by diesel in a constant volume combustion chamber - Qianming Wang; Fuxing Wei; Pengbo Dong; Ge Xiao; Zechuan Cui; Jiangping Tian; Xiuyong Shi; Wuqiang Long (Fuel, 2023)

Interaction and phase behavior of whey protein and propylene glycol alginate complex condensates - Ge Shi; Ce Shi; Yongkang Luo; Hui Hong; Jiaran Zhang; Yan Li; Yuqing Tan (Food Chemistry, 2023)

Metal-organic framework nanocrystals enabled efficient and durable two-step perovskite photovoltaics - Xiao Liang; Kang Zhou; Dawei Duan; Fei Wang; Chuangye Ge; Xianfang Zhou; Mingjian Yuan; Yumeng Shi; Haoran Lin; Quanyao Zhu; Gang Li; Hanlin Hu (Chemical Engineering Journal, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Jumping of flea beetles onto inclined platforms - Le Zong; Jianing Wu; Pingping Yang; Jing Ren; Guanya Shi; Siqin Ge; David L. Hu (Journal of Comparative Physiology A, 2023)

A belief rule-based bayesian network approach for assessing risks in the cruise supply chain: An empirical study in Shanghai, China - Jingen Zhou; Shu-Ling (Peggy) Chen; Wenming (Wendy) Shi; Son Nguyen; Maneerat Kanrak; Jiawei Ge (Ocean & Coastal Management, 2023)

Ancient DNA reveals potentially toxic cyanobacteria increasing with climate change - Jifeng Zhang; Kun Shi; Hans W. Paerl; Kathleen M. Rühland; Yanli Yuan; Rong Wang; Jie Chen; Mengjuan Ge; Lingling Zheng; Zhiping Zhang; Boqiang Qin; Jianbao Liu; et al. (Water Research, 2023)

Hyperforin: A natural lead compound with multiple pharmacological activities - Xin-Xin Li; Yu Yan; Jia Zhang; Kang Ding; Cong-Yuan Xia; Xue-Ge Pan; Yan-Jing Shi; Jie-Kun Xu; Jun He; Wei-Ku Zhang (Phytochemistry, 2023)

Enhanced washing of cadmium and lead from polluted river sediment using horizontal electroosmosis - Ran Wen; Xiong Yang; Shuang He; Jian Wu; Hongmei Ge; Zheng Chi; Yafei Shi; Shulian Wang; Andrea R. Gerson; Kewu Pi (Journal of Environmental Chemical Engineering, 2023)

Transforming municipal cotton waste into a multilayer fibre biocomposite with high strength - Yang Shi; Jinxuan Jiang; Haoran Ye; Yequan Sheng; Yihui Zhou; Shin Ying Foong; Christian Sonne; William Woei Fong Chong; Su Shiung Lam; Yanfei Xie; Jianzhang Li; Shengbo Ge (Environmental Research, 2023)

Dual metal-organic frameworks-derived Fe-atomic sites bounded to fine Fe/Fe C nanoparticles for enhanced oxygen electroreduction - Meixin Chen; Fantao Kong; Heliang Yao; Yafeng Chen; Ge Meng; Ziwei Chang; Chang Chen; Han Tian; Lianzhou Wang; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2023)

Impact of flow velocity on the heterogeneous reaction of SO2 over Fe2O3 - Yangyang Liu; Tao Wang; Qiuyue Ge; Zhuocheng Shi; Kejian Li; Kedong Gong; Lifang Xie; Wei Wang; Qianlong Wang; Jin Han; Hongbo Fu; Jianmin Chen; et al. (Atmospheric Environment, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

Comparative transcriptomic analysis of early fruit development in eggplant (Solanum melongena L.) and functional characterization of SmOVATE5 - Suli Shi; Dalu Li; Shaohang Li; Yingying Wang; Xin Tang; Yang Liu; Haiyan Ge; Huoying Chen (Plant Cell Reports, 2023)

Theoretical determination of zeta potential for the variable charge soil considering the pH variation based on the Stern-Gouy double-layer model - Xiaojuan Yang; Ge Shi; Chao Wu; Honglei Sun (Environmental Science and Pollution Research, 2023)

Occurrence and ecological risk assessment of 2,2′,4,4′-tetrabromodiphenyl ether and decabromodiphenyl ether in surface waters across China - Bin Li; Jianghong Shi; Jiawei Zhang; Huanyu Tao; Hui Ge; Mengtao Zhang; Zonglin Xu; Ruijie Xiao (Chemosphere, 2023)

Temperature-regulated and starvation-induced refractory para-toluic acid anaerobic biotransformation - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Chemosphere, 2023)

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Winter warming alleviates the severely negative effects of nitrogen addition on ecosystem stability in a Tibetan alpine grassland - Ning Zong; Ge Hou; Peili Shi; Minghua Song (Science of The Total Environment, 2023)

Redistributing interfacial charge density of Ni12P5/Ni3P via Fe doping for ultrafast urea oxidation catalysis at large current densities - Xiujuan Xu; Canhui Zhang; Jinyang Li; Hu Liu; Ge Su; Zhicheng Shi; Minghua Huang (Chemical Engineering Journal, 2023)

Supercritical water partial oxidation of indole: Reaction variables, migration pathways, and nitrogen distribution - Shi Liu; Zhiwei Ge; Mingming Du; Liejin Guo (Chemical Engineering Journal, 2023)

Assembling nanocelluloses into fibrous materials and their emerging applications - Bing Wang; Shuting Qiu; Zehong Chen; Yijie Hu; Ge Shi; Hao Zhuo; Huili Zhang; Linxin Zhong (Carbohydrate Polymers, 2023)

Inhibition of human and rat placental 3β-hydroxysteroid dehydrogenase/Δ5,4-isomerase activities by insecticides and fungicides: Mode action by docking analysis - Jingjing Li; Fuhong Tian; Yunbing Tang; Lei Shi; Shaowei Wang; Zhiyan Hu; Yang Zhu; Yiyan Wang; Huitao Li; Ren-shan Ge; Xiaoheng Li (Chemico-Biological Interactions, 2023)

Effects of waterlogging and elevated salinity on the allocation of photosynthetic carbon in estuarine tidal marsh: a mesocosm experiment - Ya-Lei Li; Zhen-Ming Ge; Li-Na Xie; Shi-Hua Li; Li-Shan Tan; Kasper Hancke (Plant and Soil, 2023)

Simple and Commercially Available 6-chloroimidazo[1,2-a]pyridine-2-carboxylic Acid-based Fluorescent Probe for Monitoring pH Changes - Yunlong Gao; Guangle Song; Guowei Shi; Jixiang Xiao; Chunhao Yuan; Yanqing Ge (Journal of Fluorescence, 2023)

A perspective from the past in conservation of plant biodiversity in central China - John Dodson; Ge Shi; Menglin Song (Environmental Monitoring and Assessment, 2023)

A Time-course Transcriptional Kinetics of Genes in Behavior, Cortisol Synthesis and Neurodevelopment in Zebrafish Larvae Exposed to Imidacloprid and Thiamethoxam - Jin-Ge Zhang; Dong-Dong Ma; Si-Ying Li; Xiao-Bing Long; Fang Liu; Zhi-Jie Lu; Wen-Jun Shi (Bulletin of Environmental Contamination and Toxicology, 2023)

Self-assembling Bioadhesive Inspired by the Fourth Repetitive Sequence of Balanus albicostatus Cement Protein 20 kDa (Balcp-20 k) - Li Jia; Yabiao Yu; Jinyang Zheng; Hao Zhou; Qiang Liu; Wei Wang; Xinxin Liu; Xiuming Zhang; Dongtao Ge; Wei Shi; Yanan Sun (Marine Biotechnology, 2022)

Recycling of bast textile wastes into high value-added products: a review - Xue Yang; Wei Fan; Hui Wang; Yang Shi; Shujuan Wang; Rock Keey Liew; Shengbo Ge (Environmental Chemistry Letters, 2022)

Double knock-in pig models with elements of binary Tet-On and phiC31 integrase systems for controllable and switchable gene expression - Qin Jin; Xiaoyu Yang; Shixue Gou; Xiaoyi Liu; Zhenpeng Zhuang; Yanhui Liang; Hui Shi; Jiayuan Huang; Han Wu; Yu Zhao; Zhen Ouyang; Quanjun Zhang; et al. (Science China Life Sciences, 2022)

Comparative genomic investigation of TCP gene family in eggplant (Solanum melongena L.) and expression analysis under divergent treatments - Dalu Li; Xin Tang; Yanxiao Dong; Yingying Wang; Suli Shi; Shaohang Li; Yang Liu; Haiyan Ge; Huoying Chen (Plant Cell Reports, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

Long-term response of an estuarine ecosystem to drastic nutrients changes in the Changjiang River during the last 59 years: A modeling perspective - Shenyang Shi; Yi Xu; Weiqi Li; Jianzhong Ge (Frontiers in Marine Science, 2022)
The riverine nutrient inputs to the ocean reflects land-use changes and can affect the health of coastal environments over time, especially for a highly-anthropogenically influenced river-estuary-shelf system. To investigate the impact of riverine inputs on the Changjiang Estuary ecosystem at a multi-decadal time scale where long-term observations are limited, we built a three-dimensional physics-biogeochemistry-coupled model system based on the Finite-Volume Community Ocean Model (FVCOM) and the European Regional Shelf Ecosystem Model (ERSEM). Our model successfully simulated the temporal and spatial nutrient variabilities in the river-estuary-shelf con7tinuum from 1960 to 2018. The results showed increasing trends of nitrate and phosphate and fluctuating silicate variability, thereby leading to rising nitrogen (N) to phosphorus (P) ratios and decreasing silicon (Si) to N and P ratios. Such changes in the stoichiometric relationship of nutrient species also alter the community structure of the primary producers in estuaries. Our model showed a general increase of diatoms over the 59 years, corresponding to decreased proportions of micro-phytoplankton and pico- phytoplankton. With different backgrounds of light and nutrient limitations in the river and inner shelf, our model suggests that the trend of the diatom proportion in the light-limited river mouth is more associated with silicate variability, with decreased diatom proportions occurring in the 2000s. Our model relates the hydroclimate, nutrient load, and biogeochemical cycling, reproducing estuarine ecosystem variability and clarifying issues such as the causality of the ecosystem interactions.

Nutritional Components, Biochemical Characteristics, Enzyme Activities, and Growth Differences of Five Freshwater Fish Species? - Xiaona Jiang; Yan Li; Jingwen Tian; Chitao Li; Yanlong Ge; Xuesong Hu; Lei Cheng; Xiaodan Shi; Lianyu Shi; Zhiying Jia (Fishes, 2022)
Common carp (Cyprinus carpio) is an economically important fish worldwide, with many of its species bred for consumption. However, there are few reports on the comprehensive comparative analysis of the muscle nutritional quality and stress resistance characteristics of different common carp species. In this study, after 15 months of feeding in the same environment, the nutritional components, serum biochemical indices, liver antioxidant and intestinal digestive enzyme activities, and muscle growth-related gene expression were determined in Songpu mirror carp (SPM; Cyprinus carpio Songpumirror), Heilongjiang wild carp (HLJ; Cyprinus carpio haematopirus), cold-resistant strain of purse red carp (CPR; Cyprinus carpio ‘Red purse cold-resistant’), Songhe carp (SH; Cyprinus carpio ‘Songhe’), and Songpu carp (SP; Cyprinus carpio Songpu). Muscle nutrient composition showed that HLJ had a significantly lower crude fat content and higher docosahexaenoic acid (DHA) + eicosapentaenoic acid (EPA) proportion than the other four common carp species (p

Protective Effect of Levilactobacillus brevis Against Yersinia enterocolitica Infection in Mouse Model via Regulating MAPK and NF-κB Pathway - Ziqi Shi; Naiyu Guan; Weijiao Sun; Tianzhi Sun; Lingdi Niu; Jinyu Li; Junwei Ge (Probiotics and Antimicrobial Proteins, 2022)

Protective Effects of Astilbin Against Cadmium-Induced Apoptosis in Chicken Kidneys via Endoplasmic Reticulum Stress Signaling Pathway - Xiuyu Li; Ming Ge; Weifeng Zhu; Panpan Wang; Jiangfeng Wang; Tiange Tai; Yuxi Wang; Jianxu Sun; Guangliang Shi (Biological Trace Element Research, 2022)

Adaptive biomineralization in two morphotypes of Sternaspidae (Annelida) from the Northern China Seas - Meiling Ge; Jing Mo; Jack Chi-Ho Ip; Yixuan Li; Wenge Shi; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2022)
Polychaetes are segmented annelid worms that play a key role in biomineralization in modern oceans. However, little is known about the underlying processes and evolutionary mechanisms. The ventro-caudal shield of Sternaspidae is a typical phosphate biomineral in annelids. Here, we investigated two sternaspids from the northern China Seas, Sternaspis chinensis and Sternaspis liui syn. n, which evolved diverse shield characteristics as local adaptation. Genetic distances, phylogenetic analyses of nuclear markers ( 18S and 28S genes), and mitochondrial genomes revealed that the latter is a junior synonym of the former. The integration of elemental composition and the transcriptomic analysis provided insights into phenotypic shield differences. The electron probe microanalysis showed that shields in S. chinensis were more biomineralized (i.e., with higher iron, phosphorus, and calcium contents) than those in S. liui syn. n. Transcriptomes of the body wall around shields determined 17,751 differentially expressed genes (DEGs) in two morphotypes of the synonymous species. Function enrichment analysis of DEGs showed that S. chinensis has an enrichment of the putative biomineralization pathways (i.e., ion transport and calmodulin binding), while S. liui syn. n consumed more energy and produced more proteins (i.e., oxidative phosphorylation and ribosome). DEGs allowed to identify seven shell matrix proteins expressed differentially in the two morphotypes, especially calponin, filamin, chitinase, and protease inhibitor BPTI/kunitz, which might contribute to shield evolutionary plasticity response to their living habitats. Overall, this study 1) revealed an environmental biomineralization adaptation in two polychaete morphotypes of one species by integrating shield chemical composition of shields and transcriptome analyses and 2) provided insights into the molecular mechanisms underlying polychaete biomineralization.

Pathological Networks Involving Dysmorphic Neurons in Type II Focal Cortical Dysplasia - Yijie Shao; Qianqian Ge; Jiachao Yang; Mi Wang; Yu Zhou; Jin-Xin Guo; Mengyue Zhu; Jiachen Shi; Yiqi Hu; Li Shen; Zhong Chen; Xiao-Ming Li; et al. (Neuroscience Bulletin, 2022)

Phthalate exposure enhances incidence of urinary incontinence: US NHANES, 2003–2004 and 2005–2006 - Xianyanling Yi; Kun Jin; Shi Qiu; Xingyu Xiong; Tianyi Zhang; Ge Peng; Dazhou Liao; Xiaonan Zheng; Hang Xu; Hong Li; Lu Yang; Qiang Wei; et al. (Environmental Science and Pollution Research, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Thermal damage and mechanical properties of high temperature sandstone with cyclic heating–cooling treatment - Shaokun Ge; Bobo Shi; Shuai Zhang; Xiaowei Zhai; Chunlei Wu (Bulletin of Engineering Geology and the Environment, 2022)

Climate change and ecological engineering jointly induced vegetation greening in global karst regions from 2001 to 2020 - Jing Huang; Zhongxi Ge; Yuqing Huang; Xuguang Tang; Zhan Shi; Peiyu Lai; Zengjing Song; Binfei Hao; Hong Yang; Mingguo Ma (Plant and Soil, 2022)

Evaluating crop coefficient and associated processes in a drip irrigation with different color of biodegradable film mulching - Ning Chen; Xianyue Li; Haibin Shi; Qi Hu; Yuehong Zhang; Qin’ge Dong; Guoshuai Wang (Irrigation Science, 2022)

Mystery revisited: Is nocturnal colored nectar a nonadaptive floral trait? - Xiang‐Hai Cai; Bao‐Bao Shi; Yang Niu; Jia Ge; Guillaume Chomicki; Gao Chen (Ecology, 2022)

Effect of toyF on wuyiencin and toyocamycin production by Streptomyces albulus CK-15 - Binghua Liu; Qiuhe Wei; Miaoling Yang; Liming Shi; Kecheng Zhang; Beibei Ge (World Journal of Microbiology and Biotechnology, 2022)

Global divergent trends of algal blooms detected by satellite during 1982–2018 - Chong Fang; Kaishan Song; Hans W Paerl; Pierre‐Andre Jacinthe; Zhidan Wen; Ge Liu; Hui Tao; Xiaofeng Xu; Tiit Kutser; Zongming Wang; Hongtao Duan; Kun Shi; et al. (Global Change Biology, 2022)
Algal blooms (ABs) in inland lakes have caused adverse ecological effects, and health impairment of animals and humans. We used archived Landsat images to examine ABs in lakes (>1 km 2 ) around the globe over a 37‐year time span (1982–2018). Out of the 176032 lakes with area >1 km 2 detected globally, 863 were impacted by ABs, 708 had sufficiently long records to define a trend, and 66% exhibited increasing trends in frequency ratio (FRQR, ratio of the number of ABs events observed in a year in a given lake to the number of available Landsat images for that lake) or area ratio (AR, ratio of annual maximum area covered by ABs observed in a lake to the surface area of that lake), while 34% showed a decreasing trend. Across North America, an intensification of ABs severity was observed for FRQR ( p p p p

QTL mapping and candidate gene prediction for fiber yield and quality traits in a high-generation cotton chromosome substitution line with Gossypium barbadense segments - Quanwei Lu; Pengtao Li; Rui Yang; Xianghui Xiao; Ziyin Li; Qiuyu Wu; Juwu Gong; Qun Ge; Aiying Liu; Shengli Du; Jundi Wang; Yuzhen Shi; et al. (Molecular Genetics and Genomics, 2022)

Identification and analysis of oil candidate genes reveals the molecular basis of cottonseed oil accumulation in Gossypium hirsutum L. - Zhibin Zhang; Juwu Gong; Zhen Zhang; Wankui Gong; Junwen Li; Yuzhen Shi; Aiying Liu; Qun Ge; Jingtao Pan; Senmiao Fan; Xiaoying Deng; Shaoqi Li; et al. (Theoretical and Applied Genetics, 2022)

Individual willingness to prepare for disasters in a geological hazard risk area: an empirical study based on the protection motivation theory - Shi-yu Hu; Miao Yu; Ting Que; Gang Fan; Hui-ge Xing (Natural Hazards, 2022)

Screening of Biological Target Molecules Related to Glucocorticoid-Induced Cataract (GIC) on the Basis of Constructing ceRNA Network - Zhan Shi; Xiumei Zhao; Ying Su; Chao Wang; Ping Liu; Hongyan Ge (Biochemical Genetics, 2022)

Characterization of Mesenchymal Stem Cells Derived from Bisphosphonate-Related Osteonecrosis of the Jaw Patients’ Gingiva - Mengyu Li; Jiajia Wang; Yejia Yu; Yuqiong Zhou; Yueqi Shi; Wenjie Zhang; Geehun Son; Jing Ge; Jun Zhao; Chi Yang; Shaoyi Wang (Stem Cell Reviews and Reports, 2022)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a clinical condition that specifically occurs in the oral cavity, characterized by retarded wound healing in oral mucosa accelerating the exposure of bone. Moreover, the pathological mechanism remains poorly understood. Gingival mesenchymal stem cells (GMSCs) play a critical role in gingival healing and soft tissue regeneration. Although previous studies have showed that bisphosphonates (BPs) are highly toxic to healthy GMSC, there is overall lack of direct evidence demonstrating the characterization of GMSCs derived from BRONJ patients. In present study, we isolated GMSCs for the first time from the central area of BRONJ patients’ gingiva (center-BRONJ GMSCs) and the peripheral area (peri-BRONJ GMSCs), and found that they exhibited decreased proliferation, adhesion, migration capacities and underwent early apoptosis in vitro compared control GMSCs. Notably, the central and peripheral BRONJ GMSCs transplantation in a mice excisional skin model also displayed lower cell survival rate and poor healing effects than that of controls. Mechanistically, TGF-β1 signaling pathway was suppressed not only in BRONJ patients’ gingival lesions but also in BRONJ GMSCs transplantation animal model. The results above suggested that under the microenvironment of BRONJ patients, the dysfunction of GMSCs and the suppressed TGF-β1 signaling pathway may be the vital factors in impaired gingival healing, thus contributing to persistent exposure of underlying bone and development of BRONJ. This study provides new insights into the prevention for BRONJ by improving the functions of GMSCs and upregulating TGF-β1 in accelerating gingival wound healing. Graphical Abstract Schematic illustration of the dysfunction of BRONJ GMSCs in vitro and BRONJ GMSCs transplantation in a mice skin model delaying cutaneous wound healing mainly via suppressing TGF-β1 signaling pathway.

A light-responsive transcription factor SmMYB35 enhances anthocyanin biosynthesis in eggplant (Solanum melongena L.) - Linzhi Li; Shaohang Li; Haiyan Ge; Suli Shi; Dalu Li; Yang Liu; Huoying Chen (Planta, 2022)

Ferrostatin-1 Alleviates White Matter Injury Via Decreasing Ferroptosis Following Spinal Cord Injury - Hongfei Ge; Xingsen Xue; Jishu Xian; Linbo Yuan; Long Wang; Yongjie Zou; Jun Zhong; Zhouyang Jiang; Jiantao Shi; Tunan Chen; Hong Su; Hua Feng; et al. (Molecular Neurobiology, 2022)

CLDASSD: Reconstructing Fine Textures of the Temperature Field Using Super-Resolution Technology - Ruian Tie; Chunxiang Shi; Gang Wan; Xingjie Hu; Lihua Kang; Lingling Ge (Advances in Atmospheric Sciences, 2022)

Characterization of a novel shrimp pathogen, Vibrio brasiliensis , isolated from Pacific white shrimp, Penaeus vannamei - Ge Li; Guosi Xie; Hailiang Wang; Xiaoyuan Wan; Xinshu Li; Chengyin Shi; Ziyan Wang; Miao Gong; Ting Li; Ping Wang; Qingli Zhang; Jie Huang (Journal of Fish Diseases, 2021)
A novel pathogenic strain Vibrio 20190611023 was isolated from the hepatopancreas of moribund cultured Penaeus vannamei suffering from black gill disease. This strain was identified as V . brasiliensis based on the phylogenetic analyses of 16S rDNA gene and five other housekeeping genes (i.e., gapA , ftsZ , mreB , topA and gyrB ). Some biochemical features of this strain were determined with an API 20NE system, and its haemolytic activity was determined using a sheep blood agar plate. The pathogenicity of this isolate 20190611023 was confirmed by the experimental challenge tests and histopathological examinations. P. vannamei were challenged via reverse gavage with different doses of bacterial suspensions. The calculated median lethal dose (LD 50 ) was (3.16 ± 1.78) × 10 5 CFU/g (body weight). Moreover, antibiotic susceptibility tests were performed, the results of which showed that the strain 20190611023 was sensitive to chloramphenicol, compound sulphamethoxazole, ciprofloxacin, doxycycline and oxacillin, but resistant to erythromycin, kanamycin, gentamicin, cefoperazone, ceftriaxone, cefamezin and piperacillin. To our knowledge, this is the first report for demonstrating V . brasiliensis as a shrimp pathogen, which expands the host range of V . brasiliensis infection. The present study highlights that more attention should be paid to this novel pathogen in intensive shrimp aquaculture.

Acrolein Induces Systemic Coagulopathy via Autophagy-dependent Secretion of von Willebrand Factor in Mice after Traumatic Brain Injury - Wenxing Cui; Xun Wu; Dayun Feng; Jianing Luo; Yingwu Shi; Wei Guo; Haixiao Liu; Qiang Wang; Liang Wang; Shunnan Ge; Yan Qu (Neuroscience Bulletin, 2021)
Traumatic brain injury (TBI)-induced coagulopathy has increasingly been recognized as a significant risk factor for poor outcomes, but the pathogenesis remains poorly understood. In this study, we aimed to investigate the causal role of acrolein, a typical lipid peroxidation product, in TBI-induced coagulopathy, and further explore the underlying molecular mechanisms. We found that the level of plasma acrolein in TBI patients suffering from coagulopathy was higher than that in those without coagulopathy. Using a controlled cortical impact mouse model, we demonstrated that the acrolein scavenger phenelzine prevented TBI-induced coagulopathy and recombinant ADAMTS-13 prevented acrolein-induced coagulopathy by cleaving von Willebrand factor (VWF). Our results showed that acrolein may contribute to an early hypercoagulable state after TBI by regulating VWF secretion. mRNA sequencing (mRNA-seq) and transcriptome analysis indicated that acrolein over-activated autophagy, and subsequent experiments revealed that acrolein activated autophagy partly by regulating the Akt/mTOR pathway. In addition, we demonstrated that acrolein was produced in the perilesional cortex, affected endothelial cell integrity, and disrupted the blood-brain barrier. In conclusion, in this study we uncovered a novel pro-coagulant effect of acrolein that may contribute to TBI-induced coagulopathy and vascular leakage, providing an alternative therapeutic target.

Exogenous Glutathione Alleviates Cadmium Toxicity in Wheat by Influencing the Absorption and Translocation of Cadmium - Ge-Zi Li; Shi-Juan Chen; Na-Ying Li; Ying-Ying Wang; Guo-Zhang Kang (Bulletin of Environmental Contamination and Toxicology, 2021)
Cadmium (Cd), a toxic heavy metal, is harmful to plants and human health. Glutathione (GSH) could alleviate Cd toxicity of plant species, whereas its mechanism responsible for wheat remains poorly understood. Here, we found that exogenous GSH application significantly increased the fresh and dry weight, root elongation, chlorophyll contents, while decreased the contents of malondialdehyde (MDA) and GSH, and translocation factor of Cd compared with Cd treatment. Moreover, GSH application significantly increased activities of antioxidant enzymes and expression of related genes, which involved in GSH synthesis, especially in roots. In addition, we found that GSH application suppressed Cd-induced expression of metal transporter genes TaNramp1 , TaNramp5 , TaHMA2 , TaHMA3 , TaLCT1 and TaIRT2 in roots. Taken together, our results suggested that GSH could alleviate Cd toxicity in wheat by increasing GSH synthesis gene expression or suppressing Cd transporter genes expression, and further affecting Cd uptake and translocation in wheat plants.

Molecular cloning and sequence characterization of common carp (Cyprinus carpio) integrin β1 (ITGβ1) and its temporal expression in response to CyHV-3 - Xiaona Jiang; Jiaxin Sun; Chitao Li; Xuesong Hu; Yanlong Ge; Bao Li; Lianyu Shi; Zhiying Jia (Aquaculture International, 2021)

Transcriptome analysis reveals hub genes in the hepatopancreas of Exopalaemon carinicauda in response to hypoxia and reoxygenation - Wenjun Shi; Pan Wang; Runhao Hu; Xihe Wan; Hui Shen; Hui Li; Libao Wang; Yi Qiao; Ge Jiang; Jie Cheng; Zeyu Yang (Aquaculture International, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Physical-property cutoffs of tight reservoirs by field and laboratory experiments: a case study from Chang 6, 8–9 in Ordos Basin - Bingbing Shi; Xiangchun Chang; Zhongquan Liu; Ye Liu; Tianchen Ge; Pengfei Zhang; Yongrui Wang; Yue Wang; Lixin Mao (Frontiers of Earth Science, 2021)

Pyrolysis characteristics of organic-rich shale from the Chang 7 member of Triassic Yanhe Profile in Ordos Basin - Zhenlong Ge; Qiang Sun; Delu Li; Qingmin Shi; Shaoni Wei; Tian Yang (Arabian Journal of Geosciences, 2021)

Projections from D2 Neurons in Different Subregions of Nucleus Accumbens Shell to Ventral Pallidum Play Distinct Roles in Reward and Aversion - Yun Yao; Ge Gao; Kai Liu; Xin Shi; Mingxiu Cheng; Yan Xiong; Sen Song (Neuroscience Bulletin, 2021)

Activated microglia–induced neuroinflammatory cytokines lead to photoreceptor apoptosis in Aβ-injected mice - Jing Wu; Ge Gao; Fanjun Shi; Hai Xie; Qian Yang; Dandan Liu; Sichang Qu; Haifeng Qin; Chaoyang Zhang; Guo-Tong Xu; Fang Liu; Jingfa Zhang (Journal of Molecular Medicine, 2021)

Influences of pika and simulated grazing disturbances on bare patches of alpine meadow in the Yellow River Source Zone - Jie-xia Li; Xi-lai Li; Jay Gao; Yan Shi; Ge-liang Ma; Ka-zhao-cai-rang (Journal of Mountain Science, 2021)

Geometric model for toppling-prone deformation of layered reverse-dip slope - Liangfu Xie; Ying Ge; Jiaqi Zhang; Shunli Tan; Bo Wang; Echuan Yan; Yongjun Qin; Jianhu Wang; Chen Shi; Guangming Yu (Natural Hazards, 2021)

Integrative analysis of differential circular RNA and long non-coding RNA profiles and associated competing endogenous RNA networks in esophageal squamous cell carcinoma - Jiang-Feng Shen; Jin-Feng Ge; Shi-Ying Zheng; Dong Jiang (Functional & Integrative Genomics, 2021)

Environment dependent microbial co‐occurrences across a cyanobacterial bloom in a freshwater lake - Gang Wu; Leixin Ge; Na Zhao; Fei Liu; Zunji Shi; Ningning Zheng; Dan Zhou; Xingpeng Jiang; Larry Halverson; Bo Xie (Environmental Microbiology, 2021)
Summary Microbial taxon–taxon co‐occurrences may directly or indirectly reflect the potential relationships between the members within a microbial community. However, to what extent and the specificity by which these co‐occurrences are influenced by environmental factors remains unclear. In this report, we evaluated how the dynamics of microbial taxon–taxon co‐occurrence is associated with the changes of environmental factors in Nan Lake at Wuhan city, China with a Modified Liquid Association method. We were able to detect more than 1000 taxon–taxon co‐occurrences highly correlated with one or more environmental factors across a phytoplankton bloom using 16S rRNA gene amplicon community profiles. These co‐occurrences, referred to as e nvironment d ependent co‐occurrences (ED_co‐occurrences), delineate a unique network in which a taxon–taxon pair exhibits specific, and potentially dynamic correlations with an environmental parameter, while the individual relative abundance of each may not. Microcystis involved ED_co‐occurrences are in important topological positions in the network, suggesting relationships between the bloom dominant species and other taxa could play a role in the interplay of microbial community and environment across various bloom stages. Our results may broaden our understanding of the response of a microbial community to the environment, particularly at the level of microbe–microbe associations.

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Farrerol maintains the contractile phenotype of VSMCs via inactivating the extracellular signal-regulated protein kinase 1/2 and p38 mitogen-activated protein kinase signaling - Enli Liu; Shasha Shi; Jie Li; Rui Ge; Taigang Liang; Qingshan Li (Molecular and Cellular Biochemistry, 2020)

A New Endoplasmic Reticulum (ER)-Targeting Fluorescent Probe for the Imaging of Cysteine in Living Cells - Lei Zhou; Yunxia Li; Aiqin Zhou; Guanghui Zhang; Zhi-Qiang Cheng; Yong-Xi Ge; Shan-Kui Liu; Ricardo Bentes Azevedo; Juan Zhang; Shenglin Jiang; Cheng-Shi Jiang (Journal of Fluorescence, 2020)

A novel variant in GPAA1, encoding a GPI transamidase complex protein, causes inherited vascular anomalies with various phenotypes - Yongyun Li; Liu Yang; Jie Yang; Jiahao Shi; Peiwei Chai; Shengfang Ge; Yefei Wang; Xianqun Fan; Renbing Jia (Human Genetics, 2020)

Identification of mecciRNAs and their roles in the mitochondrial entry of proteins - Xu Liu; Xiaolin Wang; Jingxin Li; Shanshan Hu; Yuqi Deng; Hao Yin; Xichen Bao; Qiangfeng Cliff Zhang; Geng Wang; Baolong Wang; Qinghua Shi; Ge Shan (Science China Life Sciences, 2020)

Tunneling-induced deep-seated landslides: a case study in Gulin County, Sichuan, China - Zhong Fu Wang; Feng Ge Shi; Dong Dong Li; Haoyuan Li (Arabian Journal of Geosciences, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

The characteristics of oestrone mobility in water and soil by the addition of Ca-biochar and Fe–Mn-biochar derived from Litchi chinensis Sonn. - Huan-yu Tao; Hui Ge; Jianghong Shi; Xiaowei Liu; Wei Guo; Mengtao Zhang; Yaobin Meng; Xiao-yan Li (Environmental Geochemistry and Health, 2020)

Illumina MiSeq sequencing and network analysis the distribution and co-occurrence of bacterioplankton in Danjiangkou Reservoir, China - Zhao-Jin Chen; Ge Xu; Chuan-Yu Ding; Bao-Hai Zheng; Yan Chen; Hui Han; Yu-Ying Li; Jian-Wei Shi; Lan-Qun Hu (Archives of Microbiology, 2020)

A novel research on isolation and characterization of Photobacterium damselae subsp . damselae from Pacific white shrimp, Penaeus vannamei , displaying black gill disease cultured in China - Ziyan Wang; Chengyin Shi; Hailiang Wang; Xiaoyuan Wan; Qingli Zhang; Xiaoling Song; Ge Li; Miao Gong; Shigen Ye; Guosi Xie; Jie Huang (Journal of Fish Diseases, 2020)
In June 2019, massive mortalities of cultured Penaeus vannamei occurred in a local farm in Hainan Province, China. The diseased shrimp displayed evident black gills. Three bacterial strains 20190611001, 20190611007 and 20190611022 were isolated from hepatopancreas and gills of the diseased shrimp and identified as Photobacterium damselae subsp. damselae based on the sequence analysis of 16S rRNA and toxR genes. These three isolates showed haemolytic activities. Of them, strain 20190611022 isolated from hepatopancreas was selected and processed for pathogenic analysis. The calculated median lethal dose (LD 50 ) was 9.75 ± 4.29 × 10 5 CFU/g (body weight) by challenging P. vannamei via reverse gavage. The diseased shrimp displayed enlarged hepatopancreatic tubules and sloughing of epithelial cells in tubular lumens. The strain 20190611022 was also characterized by the testing of API 20NE systems and antibiotic susceptibility. The results of disc diffusion test showed that strain 20190611022 was sensitive to chloramphenicol, compound sulfamethoxazole, cefoperazone, ceftriaxone, ceftazidime and cefuroxime. To our knowledge, this is the first report of isolation and characterization of Photobacterium damselae subsp. damselae from natural diseased P. vannamei . Our findings can serve as a basis for further studies of its pathogenicity and provide technological support for disease controlling in shrimp aquaculture.

Characterization of tropical cyclone rapid intensification under two types of El Niño events in the Western North Pacific - Donglei Shi; Xuyang Ge; Melinda Peng; Tim Li (International Journal of Climatology, 2020)
This study investigates the impacts of two different El Niño scenarios, the east Pacific warming El Niño (EPW) and the central Pacific warming El Niño (CPW), on the tropical cyclone (TC) rapid intensification (RI) in the western North Pacific (WNP). The ratio of TCs with at least one RI occurrence (RITC) to all TC numbers (RITC ratio) shows different monthly variations between the two El Niño groups. Higher RITC ratio is found during July–October (November–December) for the EPW (CPW) years. Further analyses indicate that the difference in the RITC ratio is attributed to differences in TC genesis locations, TC tracks and large‐scale environmental conditions. During July–October (TC peak season), TCs formed more in the southeastern region with EPW than with CPW. TCs in the southeastern WNP tend to move westward (northward) in the presence of weak (significant southerly) steering flow anomalies in EPW (CPW), allowing a longer (shorter) duration over the warm tropical ocean. Meanwhile, a smaller environmental vertical wind shear is also observed in the main RI region with EPW. These two mechanisms contribute to a higher peak‐season RITC ratio in the EPW years. During November–December (late season) of the EPW years, the southern WNP is dominated by anomalous anticyclonic flow that suppresses TC genesis and intensification, which leads to notably less TC frequency and RITC ratio. The anomalous equatorial heating source near the dateline induces cyclonic flow in the southeastern WNP through Gill‐type response during the late season in CPW years. The resulting larger low‐level relative vorticity, stronger upward motion, higher mid‐level relative humidity and weaker vertical wind shear all favour TCs genesis over the southeastern WNP and their subsequent intensification in the main RI region . In addition, a greater TC heat potential is evident during the late season in CPW. Hence, the more favourable atmospheric and oceanic conditions result in a greater late‐season RITC ratio in CPW than in EPW.

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Detection and molecular characterization of canine circovirus circulating in northeastern China during 2014–2016 - Lingdi Niu; Zheng Wang; Lili Zhao; Yu Wang; Xingyang Cui; Yunjia Shi; Hongyan Chen; Junwei Ge (Archives of Virology, 2020)

Antioxidative and Probiotic Activities of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China - Yunjia Shi; Xingyang Cui; Shanshan Gu; Xin Yan; Rui Li; Shuang Xia; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2019)

Dissecting the genetic basis of fiber quality and yield traits in interspecific backcross populations of Gossypium hirsutum × Gossypium barbadense - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Baocai Zhang; Qun Ge; Muhammad Jamshed; Quanwei Lu; Shaoqi Li; Xianghui Xiang; Juwu Gong; Wankui Gong; et al. (Molecular Genetics and Genomics, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

A Novel Self-Assembly Nanocrystal as Lymph Node-Targeting Delivery System: Higher Activity of Lymph Node Targeting and Longer Efficacy Against Lymphatic Metastasis - Yuling Mao; Jun Liu; Tianyu Shi; Ge Chen; Shujun Wang (AAPS PharmSciTech, 2019)

The predictive potential of altered spontaneous brain activity patterns in diabetic retinopathy and nephropathy - Yu Wang; Yi Shao; Wen-Qing Shi; Lei Jiang; Xiao-yu Wang; Pei-Wen Zhu; Qing Yuan; Ge Gao; Jin-Lei Lv; Gong-Xian Wang (EPMA Journal, 2019)

Divergence, evolution and adaptation in ray-finned fish genomes - Chao Bian; Yu Huang; Jia Li; Xinxin You; Yunhai Yi; Wei Ge; Qiong Shi (Science China Life Sciences, 2019)

Quantitative trait locus mapping for plant height and branch number in an upland cotton recombinant inbred line with an SNP-based high-density genetic map - Zhen Zhang; Aiying Liu; Zhen Huang; Senmiao Fan; Xianyan Zou; Xiaoying Deng; Qun Ge; Juwu Gong; Junwen Li; Wankui Gong; Yuzhen Shi; Liqiang Fan; et al. (Euphytica, 2019)

Global trends and future prospects of e-waste research: a bibliometric analysis - Ya Gao; Long Ge; Shuzhen Shi; Yue Sun; Ming Liu; Bo Wang; Yi Shang; Jiarui Wu; Jinhui Tian (Environmental Science and Pollution Research, 2019)

Prevalence of shrimp microsporidian parasite Enterocytozoon hepatopenaei in Jiangsu Province, China - Hui Shen; Yi Qiao; Xihe Wan; Ge Jiang; Xianping Fan; Hui Li; Wenjun Shi; Libao Wang; Xiaoran Zhen (Aquaculture International, 2019)

Evaluation of particulate matter deposition in the human respiratory tract during winter in Nanjing using size and chemically resolved ambient measurements - Xiaoyuan Liu; Dongyang Nie; Kai Zhang; Ziyao Wang; Xiaoqian Li; Zhihao Shi; Yiyi Wang; Lin Huang; Mindong Chen; Xinlei Ge; Qi Ying; Xingna Yu; et al. (Air Quality, Atmosphere & Health, 2019)

OsRhoGAP2 promoter drives inflorescence-preferential expression and confers responses to abiotic stresses in transgenic Arabidopsis - Junjun Huang; Xintian Yan; Jiajia Li; Jia Shi; Jingjing Peng; Jingyao Du; Huiwen Ge; Meina Wang; Wenjing An; Kaijie Wang; Huahua Wang; Weihong Liang (Acta Physiologiae Plantarum, 2019)

Refining ionospheric delay modeling for undifferenced and uncombined GNSS data processing - Qile Zhao; YinTong Wang; Shengfeng Gu; Fu Zheng; Chuang Shi; Maorong Ge; Harald Schuh (Journal of Geodesy, 2019)

Multi-GNSS satellite clock estimation constrained with oscillator noise model in the existence of data discontinuity - Chuang Shi; Shiwei Guo; Shengfeng Gu; Xinhao Yang; Xiaopeng Gong; Zhiguo Deng; Maorong Ge; Harald Schuh (Journal of Geodesy, 2019)

In Vitro Evaluation of Probiotic Potential of Lactic Acid Bacteria Isolated from Yunnan De’ang Pickled Tea - Zhenhui Cao; Hongbin Pan; Shijun Li; Chongying Shi; Sifan Wang; Fuyi Wang; Pengfei Ye; Junjing Jia; Changrong Ge; Qiuye Lin; Zhiyong Zhao (Probiotics and Antimicrobial Proteins, 2019)

Study on Damage and Repair Mechanical Characteristics of Rock Salt Under Uniaxial Compression - Hongwu Yin; Chunhe Yang; Hongling Ma; Xilin Shi; Xiangsheng Chen; Nan Zhang; Xinbo Ge; Wei Liu (Rock Mechanics and Rock Engineering, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Antibacterial and Antibiofilm Activity of Lactic Acid Bacteria Isolated from Traditional Artisanal Milk Cheese from Northeast China Against Enteropathogenic Bacteria - Xingyang Cui; Yunjia Shi; Shanshan Gu; Xin Yan; Hongyan Chen; Junwei Ge (Probiotics and Antimicrobial Proteins, 2018)

Silencing of miR156 confers enhanced resistance to brown planthopper in rice - Yafei Ge; Junyou Han; Guoxin Zhou; Yunmin Xu; Yue Ding; Min Shi; Changkui Guo; Gang Wu (Planta, 2018)

Genomic characterization of circoviruses associated with acute gastroenteritis in minks in northeastern China - Junwei Ge; Shanshan Gu; Xingyang Cui; Lili Zhao; Dexing Ma; Yunjia Shi; Yuanzhi Wang; Taofeng Lu; Hongyan Chen (Archives of Virology, 2018)

High-density genetic map construction and QTL mapping for fiber strength on Chr24 across multiple environments in a CCRI70 recombinant inbred lines population - Xianyan Zou; Juwu Gong; Li Duan; Xiao Jiang; Zhang Zhen; Senmiao Fan; Qun Ge; Aiying Liu; Wankui Gong; Junwen Li; Yuzhen Shi; Yanling Wang; et al. (Euphytica, 2018)

CXCL5 regulation of proliferation and migration in human non-small cell lung cancer cells - Lin Wang; Lin Shi; Jie Gu; Cheng Zhan; Junjie Xi; Jianyong Ding; Di Ge (Journal of Physiology and Biochemistry, 2018)

Genetic analysis of the fiber quality and yield traits in G. hirsutum background using chromosome segments substitution lines (CSSLs) from Gossypium barbadense - Lixue Guo; Yuzhen Shi; Juwu Gong; Aiying Liu; Yunna Tan; Wankui Gong; Junwen Li; Tingting Chen; Haihong Shang; Qun Ge; Quanwei Lu; Jie Sun; et al. (Euphytica, 2018)

Cross-neutralization of SARS coronavirus-specific antibodies against bat SARS-like coronaviruses - Lei-Ping Zeng; Xing-Yi Ge; Cheng Peng; Wanbo Tai; Shibo Jiang; Lanying Du; Zheng-Li Shi (Science China Life Sciences, 2017)

From solar terms to medical terms (Part II): Some implications for traditional Chinese Medicine - Jie Shi; Ge Chen (Science China Earth Sciences, 2017)

Identification and genetic characterization of a novel circular single-stranded DNA virus in a human upper respiratory tract sample - Lunbiao Cui; Binyao Wu; Xiaojuan Zhu; Xiling Guo; Yiyue Ge; Kangchen Zhao; Xian Qi; Zhiyang Shi; Fengcai Zhu; Lixin Sun; Minghao Zhou (Archives of Virology, 2017)

The effect of emodin on Staphylococcus aureus strains in planktonic form and biofilm formation in vitro - Xin Yan; Shanshan Gu; Yunjia Shi; Xingyang Cui; Shanshan Wen; Junwei Ge (Archives of Microbiology, 2017)

From solar terms to medical terms (Part I): A first step with big data - Ge Chen; Jie Shi (Science China Earth Sciences, 2017)

Light absorption by water-soluble organic carbon in atmospheric fine particles in the central Tibetan Plateau - YanGe Zhang; JianZhong Xu; JinSen Shi; CongHui Xie; XinLei Ge; JunFeng Wang; ShiChang Kang; Qi Zhang (Environmental Science and Pollution Research, 2017)

Influences of agricultural phenology dynamic on land surface biophysical process and climate feedback - Fengshan Liu; Ying Chen; Wenjiao Shi; Shuai Zhang; Fulu Tao; Quansheng Ge (Journal of Geographical Sciences, 2017)

The emergence of the hyperinvasive vine, Mikania micrantha (Asteraceae), via admixture and founder events inferred from population transcriptomics - Ming Yang; Ziwen He; Yelin Huang; Lu Lu; Yubin Yan; Lan Hong; Hao Shen; Ying Liu; Qiang Guo; Lu Jiang; Yanwu Zhang; Anthony J. Greenberg; et al. (Molecular Ecology, 2017)
Biological invasions that involve well‐documented rapid adaptations to new environments provide unequalled opportunities for testing evolutionary hypotheses. Mikania micrantha Kunth (Asteraceae), a perennial herbaceous vine native to tropical Central and South America, successfully invaded tropical Asia in the early 20th century. It is regarded as one of the most aggressive weeds in the world. To elucidate the molecular and evolutionary processes underlying this invasion, we extensively sampled this weed throughout its invaded range in South‐East and South Asia and surveyed its genetic structure using variants detected from population transcriptomics. Clustering results suggest that more than one source population contributed to this invasion. Computer simulations using genomewide genetic variation support a scenario of admixture and founder events during invasion. The genes differentially expressed between native and invasive populations were found to be involved in oxidative and high light intensity stress responses, pointing to a possible ecological mechanism of adaptation. Our results provide a foundation for further detailed mechanistic and population studies of this ecologically and economically important invasion. This line of research promises to provide new mitigation strategies for invasive species as well as insights into mechanisms of adaptation.

Differential expression and miRNA regulation of the GSTP1 gene in the regenerating liver of Chiloscyllium plagiosum - Yinghua Ge; Jiewen Zhang; Xinyi Shi; Conger Lu; Lingrong Yang; Yuanyuan Li; Yanna Chen; Dandan Cheng; Jing Bai; Zhengbing Lv; Lili Liu (Fish Physiology and Biochemistry, 2017)

Microbial profiles of a drinking water resource based on different 16S rRNA V regions during a heavy cyanobacterial bloom in Lake Taihu, China - Junyi Zhang; Congming Zhu; Rui Guan; Zhipeng Xiong; Wen Zhang; Junzhe Shi; Yi Sheng; Bingchuan Zhu; Jing Tu; Qinyu Ge; Ting Chen; Zuhong Lu (Environmental Science and Pollution Research, 2017)

Plant species diversity reduces N2O but not CH4 emissions from constructed wetlands under high nitrogen levels - Wenjuan Han; Mengmeng Shi; Jie Chang; Yuan Ren; Ronghua Xu; Chongbang Zhang; Ying Ge (Environmental Science and Pollution Research, 2017)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Distinct expression patterns of the GDP dissociation inhibitor protein gene (OsRhoGDI2) from Oryza sativa during development and abiotic stresses - Jun-jun Huang; Jing Zhang; Yu-fan Hao; Xin-tian Yan; Jia Shi; Gao-hua Wang; Jing-yao Du; Hui-wen Ge; Hua-hua Wang; Wei-hong Liang (Biologia, 2016)

Improving integer ambiguity resolution for GLONASS precise orbit determination - Yang Liu; Maorong Ge; Chuang Shi; Yidong Lou; Jens Wickert; Harald Schuh (Journal of Geodesy, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Nobiletin attenuates cardiac dysfunction, oxidative stress, and inflammatory in streptozotocin: induced diabetic cardiomyopathy - Ning Zhang; Zheng Yang; Shi-Zhao Xiang; Ya-Ge Jin; Wen-Ying Wei; Zhou-Yan Bian; Wei Deng; Qi-Zhu Tang (Molecular and Cellular Biochemistry, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Simultaneous Cr(VI) reduction and Zn(II) biosorption by Stenotrophomonas sp. and constitutive expression of related genes - Shimei Ge; Shi Chao Ge (Biotechnology Letters, 2016)

Comprehensive analysis of NAC transcription factors in diploid Gossypium: sequence conservation and expression analysis uncover their roles during fiber development - Haihong Shang; Zhongna Wang; Changsong Zou; Zhen Zhang; Weijie Li; Junwen Li; Yuzhen Shi; Wankui Gong; Tingting Chen; Aiying Liu; Juwu Gong; Qun Ge; et al. (Science China Life Sciences, 2016)

Up-regulation of PSMB4 is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Jiansheng Shi; Xiaorong Liu; Changde Xu; Jianbin Ge; Jianbing Ren; Jun Wang; Xinjian Song; Shirong Dai; Weidong Tao; Hongjian Lu (Journal of Molecular Histology, 2015)

Multiple Responsive Polymer-Peptide Bioconjugate - Xi-Rui Zhou; Rui Ge; Guofeng Li; Long Chen; Tianwei Tan; Xing Wang; Shi-Zhong Luo (International Journal of Peptide Research and Therapeutics, 2015)

Estimating the yaw-attitude of BDS IGSO and MEO satellites - Xiaolei Dai; Maorong Ge; Yidong Lou; Chuang Shi; Jens Wickert; Harald Schuh (Journal of Geodesy, 2015)

Identification of defense-related genes in banana roots infected by Fusarium oxysporum f. sp. cubense tropical race 4 - Weiming Li; Xuejun Ge; Wei Wu; Wei Wang; Yulin Hu; Yiwei Mo; Dequan Sun; Shengyou Shi; Jianghui Xie (Euphytica, 2015)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

Adenovirus-mediated IL-24 confers radiosensitization to human lung adenocarcinoma in vitro and in vivo - Shi-Ying Zheng; Jin-Feng Ge; Jun Zhao; Dong Jiang; Fang Li (Molecular Biology Reports, 2015)

Enhanced Phytoextraction of Heavy Metals from Contaminated Soil by Plant Co-cropping Associated with PGPR - Zhi-feng Liu; Hong-guang Ge; Chen Li; Zuo-ping Zhao; Feng-min Song; Shi-bin Hu (Water, Air, & Soil Pollution, 2015)

Complete nucleotide sequence and gene rearrangement of the mitochondrial genome of Occidozyga martensii - EN LI; XIAOQIANG LI; XIAOBING WU; GE FENG; MAN ZHANG; HAITAO SHI; LIJUN WANG; JIANPING JIANG (Journal of Genetics, 2014)

Isolation and characterization of polymorphic microsatellites for silver pomfret - YU QIN; TIANJUN XU; RIXIN WANG; GE SHI (Journal of Genetics, 2014)

Remarkable reductions of PAKs in the brain tissues of scrapie-infected rodent possibly linked closely with neuron loss - Ge Meng; Chan Tian; Hui Wang; Yin Xu; Bao-Yun Zhang; Qi Shi; Chen Gao; Cao Chen; Xue-Yu Fan; Jing Wang; Kang Xiao; Ke Ren; et al. (Medical Microbiology and Immunology, 2014)

Cascade effects of crop species richness on the diversity of pest insects and their natural enemies - PeiJian Shi; Cang Hui; XingYuan Men; ZiHua Zhao; Fang Ouyang; Feng Ge; XianShi Jin; HaiFeng Cao; B. Larry Li (Science China Life Sciences, 2014)

A pair of chiral flavonolignans as novel anti‐cyanobacterial allelochemicals derived from barley straw ( H ordeum vulgare ): characterization and comparison of their anti‐cyanobacterial activities - Xi Xiao; Haomin Huang; Zhiwei Ge; Trine B. Rounge; Jiyan Shi; Xinhua Xu; Ruobing Li; Yingxu Chen (Environmental Microbiology, 2014)
Summary The inhibitory effect of barley straw ( H ordeum vulgare ) on cyanobacteria has been observed in many field and laboratory studies for over 30 years, although the compounds responsible for this anti‐cyanobacterial effect have remained unknown. In this study, a pair of chiral flavonolignans were isolated from barley straw extract using a bioassay‐guided isolation procedure against M icrocystis sp. The structures of the allelopathic compounds were elucidated by NMR (nuclear magnetic resonance) and HPLC‐MS (high performance liquid chromatography‐mass spectrometry), and turned out to be salcolin A and B . The enantiomers differ in their anti‐cyanobacterial abilities. Both enantiomers exhibited inhibitory effects on M icrocystis sp ., and the EC 50 (concentration for 50% of maximal effect) of salcolin A and B were 6.02 × 10 −5 and 9.60 × 10 −5 mol l −1 , respectively. Furthermore, the modes of actions of the enantiomers were investigated and compared at a single cell level by flow cytometry. Salcolin A was found to induce an increase on cyanobacterial intracellular ROS (reactive oxygen species) levels and to inhibit esterase activity, whereas salcolin B caused leakages of cyanobacterial cytoplasms. Thus, salcolin A was more ‘algistatic’, and salcolin B was more ‘algicidal’. This study suggests that salcolin is the key allelochemical in barley straw's inhibitory effect on cyanobacteria and could be used as an agent in the future control of cyanobacterial harmful algae blooms.

The comparison of sensitivity of motion sickness between retinal degeneration fast mice and normal mice - Xiao-Cheng Wang; Zhao-Hui Shi; Ka Bian; Lei Zhang; Jun-Hui Xue; Guo-Qing Yang; Xue-Song Ge; Zuo-Ming Zhang (Journal of Comparative Physiology A, 2014)

Assessment of social vulnerability to natural hazards in the Yangtze River Delta, China - Yi Ge; Wen Dou; Zhihui Gu; Xin Qian; Jinfei Wang; Wei Xu; Peijun Shi; Xiaodong Ming; Xin Zhou; Yuan Chen (Stochastic Environmental Research and Risk Assessment, 2013)

Pulmonary Artery Reconstruction Using Autologous Pericardium or Azygos Venae Substitute for Surgical Treatment of Central Non-Small Cell Lung Cancer - Liu Xuegang; Shi Chao; Tang Zhen; Li Xiaojun; Liu Ge; Zhang Lei (Cell Biochemistry and Biophysics, 2013)

Genetic diversity and population structure of the marbled rockfish, Sebastiscus marmoratus, revealed by SSR markers - DIAN-QIAO SUN; GE SHI; XUE-ZHU LIU; RI-XIN WANG; TIAN-JUN XU (Journal of Genetics, 2013)

Effects of perfluorooctanesulfonate and perfluorobutanesulfonate on the growth and sexual development of Xenopus laevis - Qin-Qin Lou; Yin-Feng Zhang; Zhen Zhou; Ya-Li Shi; Ya-Nan Ge; Dong-Kai Ren; Hai-Ming Xu; Ya-Xian Zhao; Wu-Ji Wei; Zhan-Fen Qin (Ecotoxicology, 2013)

Effects of crop species richness on pest-natural enemy systems based on an experimental model system using a microlandscape - ZiHua Zhao; PeiJian Shi; XingYuan Men; Fang Ouyang; Feng Ge (Science China Life Sciences, 2013)

Dynamic analysis for gene expression profiles of endothelial colony forming cells under hypoxia - De-Cai Yu; Wen-Du Feng; Xian-Biao Shi; Zhi-Yong Wang; Wei Ge; Chun-Ping Jiang; Xi-Tai Sun; Yi-Tao Ding (Genes & Genomics, 2013)

URTK: undifferenced network RTK positioning - Xuan Zou; Maorong Ge; Weiming Tang; Chuang Shi; Jingnan Liu (GPS Solutions, 2013)

A Novel Multi-Unit Tablet for Treating Circadian Rhythm Diseases - Qi Liu; Yinhua Gong; Yun Shi; Liqun Jiang; Chunli Zheng; Liang Ge; Jianping Liu; Jiabi Zhu (AAPS PharmSciTech, 2013)

Serum microRNA expression profile as a biomarker for the diagnosis of pertussis - Yiyue Ge; Kangchen Zhao; Yuhua Qi; Xiaoyan Min; Zhiyang Shi; Xian Qi; Yunfeng Shan; Lan Cui; Minghao Zhou; Yong Wang; Hua Wang; Lunbiao Cui (Molecular Biology Reports, 2013)

Molecular cloning, characterization and expression analysis of a CC chemokine gene from miiuy croaker (Miichthys miiuy) - Yuanzhi Cheng; Yuena Sun; Ge Shi; Rixin Wang; Tianjun Xu (Fish Physiology and Biochemistry, 2012)

Expressed sequence tag analysis and cloning of trehalose-6-phosphate synthase gene from marine alga Laminaria japonica (Phaeophyta) - Jinsong Xuan; Yanbin Feng; Manli Weng; Ge Zhao; Jinfeng Shi; Jianting Yao; Xiuliang Wang; Baotai Guo; Lixian Qiao; Delin Duan; Bin Wang (Acta Oceanologica Sinica, 2012)

Association of IL23R polymorphisms with psoriasis and psoriatic arthritis: a meta-analysis - Kun-Ju Zhu; Cheng-Yao Zhu; Ge Shi; Yi-Ming Fan (Inflammation Research, 2012)

Improving the estimation of fractional-cycle biases for ambiguity resolution in precise point positioning - Jianghui Geng; Chuang Shi; Maorong Ge; Alan H. Dodson; Yidong Lou; Qile Zhao; Jingnan Liu (Journal of Geodesy, 2012)

A novel totivirus-like virus isolated from bat guano - Xinglou Yang; Yunzhi Zhang; Xingyi Ge; Junfa Yuan; Zhengli Shi (Archives of Virology, 2012)

Satellite-based carbon stock estimation for bamboo forest with a non-linear partial least square regression technique - Huaqiang Du; Guomo Zhou; Hongli Ge; Wenyi Fan; Xiaojun Xu; Weiliang Fan; Yongjun Shi (International Journal of Remote Sensing, 2012)

A meta-analysis of β1-adrenergic receptor gene polymorphisms in idiopathic dilated cardiomyopathy - Bo Jin; Qu-Zhen Ge-Shang; Yong Li; Wei Shen; Hai-Ming Shi; Huan-Chun Ni (Molecular Biology Reports, 2012)

Rapid and Sensitive Detection of Listeria monocytogenes by Loop-Mediated Isothermal Amplification - Meng-Jun Tang; Sheng Zhou; Xiao-Yan Zhang; Jun-Hua Pu; Qing-Lian Ge; Xiu-Jun Tang; Yu-Shi Gao (Current Microbiology, 2011)

Blood Lead Levels During Different Trimesters of Pregnancy and the Possible Influencing Factors in Chengdu, China - Yongmei Jiang; Haijuan Wang; Jian Chen; Ge Zhang; Lan Chen; Wei Dai; Wei Zhou; Hui Yang; Hua Shi (Biological Trace Element Research, 2011)

The complete mitochondrial genome of bighead croaker, Collichthys niveatus (Perciformes, Sciaenidae): structure of control region and phylogenetic considerations - Tian-jun Xu; Yuan-zhi Cheng; Yue-na Sun; Ge Shi; Ri-xin Wang (Molecular Biology Reports, 2011)

Bilobalide Protects Mitochondrial Function in Ovariectomized Rats by Up-regulation of mRNA and Protein Expression of Cytochrome c Oxidase Subunit I - Chun Shi; Juntao Zou; Guoying Li; Zhenying Ge; Zhibin Yao; Jie Xu (Journal of Molecular Neuroscience, 2011)

Rhizobium sphaerophysae sp. nov., a novel species isolated from root nodules of Sphaerophysa salsula in China - Lin Xu; Jian Feng Shi; Peng Zhao; Wei Min Chen; Wei Qin; Ming Tang; Ge Hong Wei (Antonie van Leeuwenhoek, 2011)

Varied association of prothrombin G20210A polymorphism with coronary artery disease susceptibility in different ethnic groups: evidence from 15,041 cases and 21,507 controls - Bo Jin; Yong Li; Qu-Zhen Ge-Shang; Huan-Chun Ni; Hai-Ming Shi; Wei Shen (Molecular Biology Reports, 2011)

Estimation of aboveground carbon stock of Moso bamboo ( Phyllostachys heterocycla var. pubescens) forest with a Landsat Thematic Mapper image - Xiaojun Xu; Huaqiang Du; Guomo Zhou; Hongli Ge; Yongjun Shi; Yufeng Zhou; Weiliang Fan; Wenyi Fan (International Journal of Remote Sensing, 2011)

A FVCOM-based unstructured grid wave, current, sediment transport model, I. Model description and validation - Lunyu Wu; Changsheng Chen; Peifang Guo; Maochong Shi; Jianhua Qi; Jianzhong Ge (Journal of Ocean University of China, 2011)

Characteristics of phytoliths in Leymus chinensis from different habitats on the Songnen Plain in Northeast China and their environmental implications - DongMei Jie; ZhaoYang Liu; LianXuan Shi; HongMei Liu; Yong Ge (Science China Earth Sciences, 2010)

Laboratory study of fluid viscosity induced ultrasonic velocity dispersion in reservoir sandstones - Tao He; Chang-Chun Zou; Fa-Gen Pei; Ke-Ying Ren; Fan-Da Kong; Ge Shi (Applied Geophysics, 2010)

Evaluating variations of genotype calling: a potential source of spurious associations in genome-wide association studies - Huixiao Hong; Zhenqiang Su; Weigong Ge; Leming Shi; Roger Perkins; Hong Fang; Donna Mendrick; Weida Tong (Journal of Genetics, 2010)

Detecting relationships between amylose content and amino acid contents of indica rice with conditional approach - Chun Hai Shi; Qiong Qiong Zhu; Ke Ming Wang; Guo Ke Ge; Jian Guo Wu; Zhen Ghao Xu (Journal of Genetics, 2010)

Spatial heterogeneity and carbon contribution of aboveground biomass of moso bamboo by using geostatistical theory - Huaqiang Du; Guomo Zhou; Wenyi Fan; Hongli Ge; Xiaojun Xu; Yongjun Shi; Weiliang Fan (Plant Ecology, 2010)

Fluid sensitivity study of elastic parameters in low-medium porosity and permeability reservoir rocks - Fa-Gen Pei; Chang-Chun Zou; Tao He; Ge Shi; Gen-Gen Qiu; Ke-Ying Ren (Applied Geophysics, 2010)

Characterization of ten microsatellite loci for the dark pomfret, Pampus cinereus (Stromateidae, Perciformes) - Li Wei; Jianxin Wang; Fanxing Meng; Ge Shi; Rixin Wang (Conservation Genetics Resources, 2009)

Development and characterization of microsatellite markers for a mangrove tree species Sonneratia caseolaris (L.) Engler (Lythraceae sensu lato) - Tao Chen; Renchao Zhou; Xue-Jun Ge; Suhua Shi (Conservation Genetics, 2008)

Resolution of GPS carrier-phase ambiguities in Precise Point Positioning (PPP) with daily observations - M. Ge; G. Gendt; M. Rothacher; C. Shi; J. Liu (Journal of Geodesy, 2008)

Resolution of GPS carrier-phase ambiguities in Precise Point Positioning (PPP) with daily observations - M. Ge; G. Gendt; M. Rothacher; C. Shi; J. Liu (Journal of Geodesy, 2008)

Overexpression of the trehalose-6-phosphate phosphatase gene OsTPP1 confers stress tolerance in rice and results in the activation of stress responsive genes - Liang-Fa Ge; Dai-Yin Chao; Min Shi; Mei-Zhen Zhu; Ji-Ping Gao; Hong-Xuan Lin (Planta, 2008)

Characterization of seven genomic and one dbEST-derived microsatellite loci in the river mangrove Aegiceras corniculatum (Myrsinaceae) - Guo-Qing Chen; Lin-Feng Li; Gang Hao; Su-Hua Shi; Xue-Jun Ge (Conservation Genetics, 2008)

Morphological and behavioral consequences of recurrent seizures in neonatal rats are associated with glucocorticoid levels - Xiu-Yu Shi; Ji-Wen Wang; Ge-Fei Lei; Ruo-Peng Sun (Neuroscience Bulletin, 2007)

The dynamic gene expression from different genetic systems for protein and lysine contents of indica rice - C. H. Shi; G. K. Ge; J. G. Wu; J. Ye; P. Wu (Genetica, 2006)

Genetic Diversity and Population Differentiation of Liaoning Weedy Rice Detected by RAPD and SSR Markers - Guo-qin Yu; Ying Bao; Chun-hai Shi; Chang-qin Dong; Song Ge (Biochemical Genetics, 2005)

Measurement of agglomeration economies at County level in Jiangsu Province - Ying Ge; Ying-xia Pu; Shi-mou Yao (Chinese Geographical Science, 2005)